Catalysts for selective catalytic reduction of NOx and decomposition and conversion of hydrocarbons

JP2024518352A5Pending Publication Date: 2025-05-08BASF CORPORATON
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2023566778
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-04-28
Filing Date
2022-04-27
Publication Date
2025-05-08

AI Technical Summary

Technical Problem

Existing catalysts for selective catalytic reduction of NOx and hydrocarbon conversion suffer from sulfidation deactivation, leading to inadequate denitrification and emissions, particularly in the absence of an upstream oxidation catalyst.

Method used

A catalyst comprising a substrate coated with an 8-membered ring porous zeolite material containing platinum group metals, copper, and iron, along with a non-zeolitic oxide material, which is designed to recover catalytic performance after sulfidation deactivation.

Benefits of technology

The catalyst effectively recovers catalytic properties post-sulfidation, enhancing NOx reduction and hydrocarbon conversion efficiency while maintaining emissions compliance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000061_0000
    Figure 00000061_0000
  • Figure 00000061_0001
    Figure 00000061_0001
  • Figure 00000061_0002
    Figure 00000061_0002
Patent Text Reader

Abstract

The present invention relates to a catalyst for selective catalytic reduction of NOx and cracking and conversion of hydrocarbons comprising: a substrate including an inlet end, an outlet end, an axial length of the substrate extending from the inlet end to the outlet end, and a plurality of passages defined by an interior wall of the substrate extending therethrough; and a coating disposed on a surface of the interior wall of the substrate, the coating comprising an 8-ring porous zeolite material comprising a platinum group metal, and one or more of copper and iron, and further comprising a 10-ring or greater porous zeolite material.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a catalyst for selective catalytic reduction of NOx and decomposition and conversion of hydrocarbons, and an exhaust gas treatment system comprising said catalyst and a downstream second catalyst.Furthermore, the present invention relates to a method for preparing said catalyst, a method for using said catalyst and said system, and a method for simultaneously converting NOx and HC.Furthermore, the present invention relates to a catalyst for selective catalytic reduction of NOx, ammonia oxidation, and decomposition and conversion of hydrocarbons, and an exhaust gas treatment system comprising said catalyst.

[0002] WO 2018 / 224651 A2 relates to an exhaust gas treatment system comprising a first catalyst for the abatement of HC and NOx comprising a palladium and Cu-zeolite material followed by a second catalyst downstream thereof comprising a NOx reducing component and an ammonia oxidizing component.

[0003] US 10,589,261 B2 discloses an exhaust system having a first zone containing a first SCR catalyst and a second zone containing an ammonia slip catalyst (ASC), the ammonia slip catalyst containing a second SCR catalyst and an oxidation catalyst, the ASC having a diesel oxidation catalyst (DOC) function, the first zone being located on the inlet side of a substrate and the second zone being located on the outlet side of the substrate.

[0004] Furthermore, it is a known issue that close-coupled selective catalytic reduction (SCR) catalysts based on copper-containing zeolite materials with CHA-type framework structures can sulfurize over time due to sulfur trioxide (SO3) emitted from the engine and generated internally by the SCR catalyst, despite the absence of an upstream oxidation catalyst. Here, the term "close-coupled" catalyst is used to define the first catalyst that receives the exhaust gas stream emitted from the engine. Thus, it results in the close-coupled SCR catalyst being unable to provide sufficient denitration to meet ultra-low nitrogen oxide (NOx) and nitrous oxide (N2O) emissions such as CARB after sulfation. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] WO 2018 / 224651 A2 [Patent Document 2] US 10,589,261 B2 Summary of the Invention [Problem to be solved by the invention]

[0006] It was therefore an object of the present invention to provide a catalyst for the selective catalytic reduction of NOx and the decomposition and conversion of hydrocarbons, which exhibits improved catalytic properties and can be fully restored after sulfation deactivation. [Means for solving the problem]

[0007] Surprisingly, it has been found that the catalysts of the present invention for the selective catalytic reduction of NOx and the decomposition and conversion of hydrocarbons exhibit improved catalytic properties and can be fully restored after sulfidation deactivation.

[0008] Thus, the present invention provides (i) a substrate including an inlet end, an outlet end, an axial length of the substrate extending from the inlet end to the outlet end, and a plurality of passages defined by an interior wall of the substrate extending therethrough; (ii) a coating disposed on a surface of an inner wall of a substrate, the coating comprising an 8-ring porous zeolite material comprising a platinum group metal and one or more of copper and iron, and further comprising a 10 or more ring porous zeolite material. The present invention relates to catalysts for the selective catalytic reduction of NOx, and the cracking and conversion of hydrocarbons, including [Brief description of the drawings]

[0009] [Figure 1] Figure 1 shows the test conditions for the two exhaust gas treatment systems. [Diagram 2]Figure 2 shows the test conditions for the two exhaust gas treatment systems. [Diagram 3] Figure 3 shows the test conditions for the two exhaust gas treatment systems. [Figure 4] FIG. 4 shows the different temperatures obtained at the outlet end of catalyst 1 and catalyst 2 of the comparative system when catalyst 1 inlet temperatures of 305° C., 325° C. and 350° C. are applied. [Diagram 5] FIG. 5 shows the different temperatures obtained at the outlet end of catalyst 1 and catalyst 2 of the system of the invention when applying catalyst 1 inlet temperatures of 305° C., 325° C. and 350° C. [Figure 6] FIG. 6 shows the HC slip at the outlet end of catalyst 1 and catalyst 2 for the comparative system when catalyst 1 inlet temperatures of 305° C., 325° C. and 350° C. are applied. [Figure 7] FIG. 7 shows the HC slip at the outlet end of catalyst 1 and catalyst 2 of the system of the present invention when catalyst 1 inlet temperatures of 305° C., 325° C. and 350° C. are applied. [Figure 8] FIG. 8 shows the DeNOx measured at low and high temperatures for the catalysts of Examples 10 and 12-15. [Figure 9] FIG. 9 shows the N2O production measured at low and high temperatures for the catalysts of Examples 10 and 12-15. [Figure 10] FIG. 10 shows the NH3 slip measured at low and high temperatures for the catalysts of Examples 10 and 12-15. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] Preferably, the platinum group metal contained in coating (ii) is selected from the group consisting of palladium, platinum, rhodium, iridium and osmium, more preferably selected from the group consisting of palladium, platinum and rhodium, more preferably selected from the group consisting of palladium and platinum, more preferably the platinum group metal contained in coating (ii) is palladium.

[0011] Preferably the coating has a coating weight of 2 to 100 g / ft, calculated as elemental platinum group metal. 3 More preferably, the range is 5 to 80 g / ft 3 More preferably, the range is 7 to 60 g / ft 3 More preferably, the range is 8 to 40 g / ft 3 More preferably, it is in the range of 10 to 30 g / ft 3 The platinum group metal is included in the carrier at a loading in the range of 0.1 to 1000 ppm.

[0012] With regard to coating (ii), it is preferred that it further comprises a non-zeolitic oxide material comprising one or more of alumina, zirconia, silica, titania and ceria, more preferably one or more of alumina, zirconia and silica, more preferably one or more of alumina and zirconia, more preferably alumina or zirconia.

[0013] The non-zeolitic oxide material preferably comprises 30 to 100 mass%, more preferably 50 to 99 mass%, more preferably 70 to 95 mass%, more preferably 80 to 92 mass% of zirconia. The non-zeolitic oxide material preferably comprises 5 to 15 mass%, more preferably 6 to 12 mass% of lanthanum calculated as La2O3.

[0014] Preferably, the 8-ring porous zeolitic material contained in coating (ii) has a framework type selected from the group consisting of CHA, AEI, RTH, LEV, DDR, KFI, ERI, AFX, mixtures of two or more thereof, and mixed types of two or more thereof, more preferably selected from the group consisting of CHA, AEI, RTH, AFX, mixtures of two or more thereof, and mixed types of two or more thereof, more preferably selected from the group consisting of CHA and AEI. More preferably, the 8-ring porous zeolitic material contained in coating (ii) has framework type CHA.

[0015] The framework structure of the 8-membered ring porous zeolite material is composed of Si, Al and O in an amount of preferably 95 to 100 mass%, more preferably 98 to 100 mass%, more preferably 99 to 100 mass%, and more preferably 99.5 to 100 mass%.

[0016] The framework structure of the zeolite material is preferably composed of P in a maximum of 1 mass %, more preferably 0 to 0.5 mass %, and more preferably 0 to 0.1 mass %.

[0017] Preferably, in the framework of the 8-membered ring porous zeolite material, the molar ratio of Si to Al calculated as molar SiO2:Al2O3 is in the range of 2:1 to 60:1, more preferably in the range of 2:1 to 50:1, more preferably in the range of 5:1 to 40:1, more preferably in the range of 10:1 to 35:1, more preferably in the range of 15:1 to 33:1. In the framework of the 8-membered ring porous zeolite material, the molar ratio of Si to Al calculated as molar SiO2:Al2O3 is more preferably in the range of 15:1 to 20:1. Alternatively, in the framework of the 8-membered ring porous zeolite material, the molar ratio of Si to Al calculated as molar SiO2:Al2O3 is more preferably in the range of 25:1 to 33:1.

[0018] Preferably, the 8-ring porous zeolitic material contained in coating (ii), more preferably having framework type CHA, has an average crystallite size as determined by scanning electron microscopy of at least 0.1 micrometer, more preferably in the range of 0.1 to 3.0 micrometer, more preferably in the range of 0.3 to 1.5 micrometer, more preferably in the range of 0.4 to 1.0 micrometer.

[0019] Preferably, the coating (ii) has a coating density of 0.1 to 3.0 g / in 3 More preferably, the range is 0.5 to 2.5 g / in 3 More preferably, the range is 0.7 to 2.2 g / in 3 More preferably, the range is 0.8 to 2.0 g / in 3 The zeolite material is included at loadings in the range of 0.1 to 1000 μg / kg.

[0020] Preferably, the 8-ring porous zeolitic material contained in coating (ii) comprises copper, wherein said coating comprises copper in an amount, calculated as CuO, based on the weight of the 8-ring porous zeolitic material contained in coating (ii), more preferably in the range of 1 to 15% by weight, more preferably in the range of 1.25 to 10% by weight, more preferably in the range of 1.5 to 7% by weight, more preferably in the range of 2 to 6% by weight, more preferably in the range of 2.5 to 5.5% by weight.

[0021] Preferably, the porous zeolitic material with 10 or more ring members contained in the coating (ii) is selected from the group consisting of FER, MFI, BEA, MWW, AFI, MOR, OFF, MFS, MTT, FAU, LTL, MEI, MOR, mixtures of two or more thereof and mixed types of two or more thereof, more preferably selected from the group consisting of FAU, FER, MFI, BEA, MWW, MOR, mixtures of two or more thereof and mixed types of two or more thereof, more preferably selected from the group consisting of FAU, FER, MFI and BEA. More preferably, the porous zeolitic material with 10 or more ring members, more preferably 10 or 12 ring members, is a zeolitic material with framework type FAU or FER or MFI or BEA.

[0022] The framework structure of the porous zeolite material having 10 or more membered rings is composed of Si, Al and O in an amount of preferably 95 to 100 mass%, more preferably 98 to 100 mass%, more preferably 99 to 100 mass%, and more preferably 99.5 to 100 mass%.

[0023] The framework structure of the porous zeolite material having 10 or more ring members is preferably composed of P at a maximum of 1 mass %, more preferably 0 to 0.5 mass %, and more preferably 0 to 0.1 mass %.

[0024] Preferably, in the framework structure of the porous zeolite material having 10 or more ring members, the molar ratio of Si to Al calculated as molar SiO2:Al2O3 is in the range of 2:1 to 60:1, more preferably in the range of 3:1 to 40:1, and more preferably in the range of 3:1 to 35:1.

[0025] Preferably, the porous zeolitic material with 10 or more membered rings contained in coating (ii) is a zeolitic material having framework type BEA, wherein in the framework structure of said zeolitic material the molar ratio of Si to Al, calculated as molar SiO2:Al2O3, is in the range of 4:1 to 20:1, more preferably in the range of 6:1 to 15:1, more preferably in the range of 8:1 to 12:1.

[0026] Alternatively, preferably, the 10 or more membered ring porous zeolitic material comprised in coating (ii) is a zeolitic material having framework type FER, wherein in the framework structure of said zeolitic material, the molar ratio of Si to Al, calculated as molar SiO2:Al2O3, is in the range of 10:1 to 30:1, more preferably in the range of 15:1 to 25:1, more preferably in the range of 18:1 to 22:1.

[0027] Alternatively, preferably, the porous zeolitic material having 10 or more membered rings contained in coating (ii) is a zeolitic material having framework type FAU, wherein in the framework structure of said zeolitic material, the molar ratio of Si to Al, calculated as molar SiO2:Al2O3, is in the range of 3:1 to 15:1, more preferably in the range of 4:1 to 10:1, more preferably in the range of 4:1 to 8:1.

[0028] Alternatively, preferably, the 10 or more membered ring porous zeolitic material comprised in coating (ii) is a zeolitic material having framework type MFI, wherein in the framework structure of said zeolitic material, the molar ratio of Si to Al, calculated as molar SiO2:Al2O3, is in the range of 10:1 to 35:1, more preferably in the range of 20:1 to 32:1, more preferably in the range of 25:1 to 30:1.

[0029] In the context of the present invention, the porous zeolitic material with 10 or more ring members contained in coating (ii) preferably comprises one or more of iron, copper and rare earth element components, more preferably one or more of iron and rare earth element components. Alternatively, the porous zeolitic material with 10 or more ring members contained in coating (ii) is preferably in its H-form.

[0030] More preferably, coating (ii) contains one or more of the iron, copper and rare earth element components, calculated as the respective oxides, in an amount preferably in the range of 1 to 20 mass %, more preferably in the range of 5 to 20 mass %, more preferably in the range of 2 to 8 mass %, or more preferably in the range of 10 to 20 mass %, based on the mass of the porous zeolite material having 10 or more ring members contained in coating (ii).

[0031] Preferably, the zeolite material contained in coating (ii) contains iron. Preferably, when the porous zeolite material having 10 or more ring members contained in coating (ii) contains iron, coating (ii) contains iron in an amount in the range of 2 to 8 mass %, more preferably in the range of 2.5 to 6 mass %, more preferably in the range of 3 to 5.5 mass %, calculated as Fe2O3, based on the mass of the porous zeolite material having 10 or more ring members contained in coating (ii).

[0032] Alternatively, and preferably, the zeolitic material contained in coating (ii) comprises a rare earth component, preferably comprising one or more of La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Er, Y and Yb, more preferably comprising one or more of La, Ce, Pr, Nd, Sm, Eu, Y, Yb and Gd, more preferably comprising one or more of La and Ce.

[0033] More preferably, 60 to 100 mass %, more preferably 80 to 100 mass % of the rare earth element component is La and / or Ce. In other words, it is preferred that La and / or Ce is the main element(s) in the rare earth element component contained in the coating (ii).

[0034] Preferably, when the porous zeolite material having 10 or more ring members contained in coating (ii) contains a rare earth element component, coating (ii) contains the rare earth element component in an amount in the range of 10 to 20% by mass, more preferably in the range of 12 to 18% by mass, more preferably in the range of 14 to 17% by mass, calculated as the respective oxide(s), based on the mass of the porous zeolite material having 10 or more ring members contained in coating (ii).

[0035] Preferably, the coating (ii) extends over 95-100%, more preferably 98-100%, more preferably 99-100% of the axial length of the substrate.

[0036] Preferably, the coating according to (ii) (ii.1) an inlet coat comprising a platinum group metal and a porous zeolite material having 10 or more ring members; and (ii.2) an outlet coat comprising an 8-ring porous zeolitic material containing a platinum group metal, a non-zeolitic oxide material, more preferably as defined above, and one or more of copper and iron; and more preferably consisting of the above, wherein the inlet coat (ii.1) extends from the inlet end to the outlet end of the substrate according to (i) over x % of the axial length of the substrate, where x is in the range of 20 to 80, more preferably 30 to 60; The outlet coat (ii.2) extends from the outlet end towards the inlet end of the substrate according to (i) over y% of the axial length of the substrate, where y is in the range 20-80, more preferably 30-60.

[0037] Preferably, the inlet coat (ii.1) is disposed on the inner wall surface of the substrate (i) and preferably the outlet coat (ii.2) is disposed on the inner wall surface of the substrate (i), and y is 100-x.

[0038] Preferably, the platinum group metal contained in the inlet coat (ii.1) is supported on a porous zeolitic material having 10 or more ring members and containing one or more of the following components: iron, copper and rare earth elements.

[0039] Preferably, the platinum group metal in the inlet coat (ii.1) is palladium and the 10 or more ring porous zeolitic material in the inlet coat (ii.1) is a zeolitic material with framework type BEA, wherein said zeolitic material more preferably comprises one or more of iron, copper and rare earth components, more preferably one or more of iron and rare earth components, more preferably iron. Alternatively, preferably, the platinum group metal in the inlet coat (ii.1) is palladium and the 10 or more ring porous zeolitic material in the inlet coat (ii.1) is a zeolitic material with framework type FAU, wherein said zeolitic material more preferably comprises one or more of iron, copper and rare earth components, more preferably one or more of iron and rare earth components, more preferably a rare earth component as defined above. Alternatively, preferably, the platinum group metal in the inlet coat (ii.1) is palladium and the 10 or more ring porous zeolitic material in the inlet coat (ii.1) is a zeolitic material having framework type MFI, more preferably wherein said zeolitic material comprises one or more of iron, copper and rare earth element components, more preferably one or more of iron and rare earth element components, more preferably iron.

[0040] In the context of the present invention, preferably 99 to 100% by weight, more preferably 99.5 to 100% by weight, more preferably 99.9 to 100% by weight of the inlet coat (ii.1) consists of one or more of the platinum group metals, the porous zeolitic material having 10 or more ring members, and more preferably iron, copper and rare earth element components.

[0041] Preferably, inlet coat (ii.1) further comprises a non-zeolitic oxidic material, more preferably a non-zeolitic oxidic material as defined above, wherein the platinum group metal comprised in inlet coat (ii.1) is supported on said non-zeolitic oxidic material, and inlet coat (ii.1) comprises the non-zeolitic oxidic material more preferably in an amount in the range of 5 to 50% by weight, more preferably in the range of 10 to 50% by weight, based on the weight of inlet coat (ii.1).

[0042] Preferably, the platinum group metal in the inlet coat (ii.1) is palladium, the non-zeolitic oxide material comprises zirconia or alumina and the 10 or more ring porous zeolitic material in the inlet coat (ii.1) is a zeolitic material with framework type BEA, more preferably comprising one or more of iron, copper and rare earth element components, more preferably one or more of iron and rare earth element components, more preferably iron. Alternatively, preferably, the zeolitic material with framework type BEA is in the H-form.

[0043] Preferably, 99 to 100% by mass, more preferably 99.5 to 100% by mass, more preferably 99.9 to 100% by mass of the inlet coat (ii.1) consists of one or more of platinum group metals, non-zeolitic oxide materials, porous zeolitic materials with 10 or more ring members, and optionally iron, copper and rare earth element components.

[0044] Preferably, the inlet coat (ii.1) has a metal content of 5 to 40 g / ft, calculated as elemental platinum group metal. 3 More preferably, it is in the range of 10 to 35 g / ft 3 More preferably, it is in the range of 15 to 30 g / ft 3 The platinum group metal is included in the carrier at a loading in the range of 0.1 to 1000 ppm.

[0045] Preferably, the inlet coat (ii.1) has a coating density of 1 to 2 g / in 3 More preferably, the range is 1.1 to 1.5 g / in 3 The zeolite material is included at loadings in the range of 0.1 to 1000 μg / kg.

[0046] Preferably, at most 0.1% by weight, more preferably at most 0.01% by weight, more preferably at most 0.001% by weight of the inlet coat (ii.1) consists of 8-ring porous zeolitic material, in other words, preferably, the inlet coat (ii.1) is substantially free of 8-ring porous zeolitic material, more preferably, is substantially free of 8-ring porous zeolitic material.

[0047] Preferably, the platinum group metal of the outlet coat (ii.2) is supported on the non-zeolitic oxidic material of the outlet coat (ii.2).

[0048] Preferably, the exit coat (ii.2) has a coating density of 0.05 to 1 g / in 3 More preferably, the range is 0.1 to 0.5 g / in 3 The non-zeolitic oxide materials are included at loadings in the range of 0.1 to 1.0.

[0049] Preferably, the mass ratio of the 8-ring porous zeolitic material of the outlet coat (ii.2) to the non-zeolitic oxide material of the outlet coat (ii.2) is in the range of 3:1 to 20:1, more preferably in the range of 5:1 to 15:1, more preferably in the range of 8:1 to 12:1.

[0050] Preferably, in the framework structure of the 8-ring porous zeolitic material of the outlet coat (ii.2), the molar ratio of Si to Al, calculated as molar SiO2:Al2O3, is in the range of 15:1 to 33:1, more preferably in the range of 15:1 to 20:1, or more preferably in the range of 25:1 to 33:1.

[0051] Preferably, the 8-ring porous zeolitic material contained in the outlet coat (ii.2) comprises copper, wherein said outlet coat (ii.2) comprises copper in an amount, calculated as CuO, based on the weight of the 8-ring porous zeolitic material contained in the outlet coat (ii.2), more preferably in the range of 2.5 to 5.5% by weight, more preferably in the range of 2.75 to 5.5% by weight, more preferably in the range of 3 to 3.75% by weight, or more preferably in the range of 4.5 to 5.25% by weight.

[0052] Preferably, the platinum group metal in the outlet coat (ii.2) is palladium and the non-zeolitic oxide material of the outlet coat (ii.2) comprises zirconia.

[0053] Preferably, the exit coat (ii.2) has a metal content of 5 to 25 g / ft, calculated as elemental platinum group metal. 3 More preferably, it is in the range of 10 to 20 g / ft 3 The platinum group metal is included in the carrier at a loading in the range of 0.1 to 1000 ppm.

[0054] Preferably, the exit coat (ii.2) has a density of 1 to 4 g / in 3 More preferably, in the range of 1.5 to 2.5 g / in 3 The zeolite material includes 8-ring porous material at loadings in the range of 100 to 2000 nm.

[0055] Preferably, the exit coat (ii.2) further comprises a metal oxide binder, wherein the metal oxide binder more preferably comprises one or more of zirconia, alumina, titania, silica and mixed oxides comprising two or more of Zr, Al, Ti and Si, more preferably one or more of alumina and zirconia, more preferably zirconia.

[0056] Preferably, the outlet coat (ii.2) comprises said metal oxide binder in an amount in the range of 1 to 8% by weight, more preferably in the range of 3 to 7% by weight, based on the weight of the 8-ring porous zeolitic material containing one or more of copper and iron.

[0057] Preferably, 99 to 100% by mass, more preferably 99.5 to 100% by mass, more preferably 99.9 to 100% by mass of the outlet coat (ii.2) consists of an 8-ring porous zeolitic material comprising one or more of a platinum group metal, a non-zeolitic oxide material, copper and iron, and more preferably a metal oxide binder as defined above.

[0058] Preferably at most 0.1% by weight, more preferably at most 0.01% by weight, more preferably at most 0.001% by weight of the outlet coat (ii.2) consists of porous zeolitic material with 10 or more ring members, in other words preferably the outlet coat (ii.2) is substantially free of porous zeolitic material with 10 or more ring members, more preferably free of porous zeolitic material with 10 or more ring members.

[0059] Alternatively and preferably, the coating according to (ii) (ii.1) an inlet coat comprising a porous zeolitic material having 10 or more ring members, wherein at most 0.1% by weight of the inlet coat (ii.1) is made of platinum group metals, more preferably at most 0.01% by weight, more preferably at most 0.001% by weight; and (ii.2) an outlet coat comprising an 8-ring porous zeolitic material containing a platinum group metal, a non-zeolitic oxide material, more preferably as defined above, and one or more of copper and iron; and more preferably consisting of the above, wherein the inlet coat (ii.1) extends from the inlet end to the outlet end of the substrate according to (i) over x % of the axial length of the substrate, where x is in the range of 20 to 80, more preferably 30 to 60; The outlet coat (ii.2) extends from the outlet end towards the inlet end of the substrate according to (i) over y % of the axial length of the substrate, with y being in the range of from 20 to 80, more preferably from 30 to 60. In terms of the composition of the inlet coat, in other words the inlet coat (ii.1) is preferably substantially free of platinum group metals, more preferably free of platinum group metals.

[0060] Alternatively and preferably, the coating according to (ii) (ii.1) an inlet coat comprising a platinum group metal and a porous zeolite material having 10 or more ring members; and (ii.2) an outlet coat comprising a non-zeolitic oxide material, more preferably as defined above, and an 8-ring porous zeolitic material containing one or more of copper and iron; and more preferably consisting of the above, wherein the inlet coat (ii.1) extends from the inlet end to the outlet end of the substrate according to (i) over x % of the axial length of the substrate, where x is in the range of 20 to 80, more preferably 30 to 60; The outlet coat (ii.2) extends from the outlet end towards the inlet end of the substrate according to (i) over y % of the axial length of the substrate, with y being in the range of from 20 to 80, more preferably from 30 to 60. In terms of the composition of the outlet coat, in other words the outlet coat (ii.2) is preferably substantially free of platinum group metals, more preferably free of platinum group metals.

[0061] In the context of the present invention, alternatively and preferably, coating (ii) is a single coat.

[0062] Preferably, the non-zeolitic oxide material of coating (ii) comprises zirconia or alumina, wherein coating (ii) has a surface area of ​​preferably 0.05 to 1 g / in 3 , more preferably 0.1 to 0.5 g / in 3 The non-zeolitic oxide material is preferably present in a loading range of 0.1 to 1.0 μg / kg.

[0063] Preferably, in the framework structure of the 8-ring porous zeolitic material of coating (ii), the molar ratio of Si to Al, calculated as molar SiO2:Al2O3, is more preferably in the range of 15:1 to 20:1.

[0064] Preferably, the 8-ring porous zeolitic material contained in coating (ii) comprises copper, wherein said coating comprises copper in an amount, calculated as CuO, based on the weight of the 8-ring porous zeolitic material contained in coating (ii), more preferably in the range of 2.5 to 5.5% by weight, more preferably in the range of 4.5 to 5.25% by weight.

[0065] Preferably, the mass ratio of the 8-ring porous zeolitic material of coating (ii) to the non-zeolitic oxide material of coating (ii) is in the range of 2:1 to 15:1, more preferably in the range of 3:1 to 12:1, more preferably in the range of 5:1 to 9:1.

[0066] Preferably, the mass ratio of the 8-membered ring porous zeolite material of coating (ii) to the 10 or more membered ring porous zeolite material of coating (ii) is in the range of 2:1 to 15:1, more preferably in the range of 3:1 to 12:1, more preferably in the range of 5:1 to 9:1.

[0067] Preferably, the 8-ring porous zeolitic material of coating (ii) has framework type CHA and the 10 or more ring porous zeolitic material of coating (ii) has framework type BEA and contains iron.

[0068] Alternatively, preferably, the 8-ring porous zeolitic material of coating (ii) has framework type CHA and the 10 or more ring porous zeolitic material of coating (ii) has framework type FAU and comprises a rare earth element component as defined above.

[0069] Alternatively, preferably, the 8-ring porous zeolitic material of coating (ii) has framework type CHA and the 10 or more ring porous zeolitic material of coating (ii) has framework type MFI and contains iron.

[0070] Alternatively, preferably, the 8-ring porous zeolitic material of coating (ii) has framework type CHA and the 10 or more ring porous zeolitic material of coating (ii) has framework type FER.

[0071] Preferably, the coating (ii) further comprises a metal oxide binder, wherein the metal oxide binder more preferably comprises one or more of zirconia, alumina, titania, silica, and mixed oxides comprising two or more of Zr, Al, Ti and Si, more preferably one or more of alumina and zirconia, more preferably zirconia.

[0072] Preferably, the coating (ii) comprises a metal oxide binder, preferably in an amount in the range of 1 to 8 mass %, more preferably in the range of 3 to 7 mass %, based on the mass of the 8-ring porous zeolitic material containing one or more of copper and iron.

[0073] Preferably, 99 to 100% by mass, more preferably 99.5 to 100% by mass, more preferably 99.9 to 100% by mass of coating (ii) consists of a 10 or more ring-membered porous zeolite material optionally containing one or more of iron, copper and rare earth element components, an 8-ring-membered porous zeolite material containing one or more of platinum group metals, copper and iron, more preferably a non-zeolitic oxide material as defined above, and more preferably a metal oxide binder as defined above.

[0074] The substrate (i) is preferably a flow-through substrate or a wall-flow filter substrate, more preferably a flow-through substrate.

[0075] Preferably, the flow-through substrate (i) comprises a ceramic material, more preferably consists of a ceramic material, where the ceramic material more preferably comprises one or more of alumina, silica, silicate, aluminosilicate, more preferably cordierite or mullite, aluminotitanate, silicon carbide, zirconia, magnesia, more preferably spinel, and titania, more preferably one or more of silicon carbide and cordierite, more preferably cordierite, more preferably consists of the above. In the context of the present invention, the catalyst of the present invention, preferably comprising a ceramic substrate, can be placed downstream of an uncoated / catalytically inactive electric heating device in an exhaust gas treatment system.

[0076] Alternatively, preferably, the flow-through substrate (i) comprises a metal material, more preferably consists of a metal material. There is no particular limitation on the substrate of the catalyst comprising a metal substrate, more preferably consists of a metal substrate, as long as the substrate is suitable for the intended use of the catalyst of the present invention. Preferably, the metal substrate comprises oxygen and one or more of iron, chromium and aluminum, more preferably consists of oxygen and one or more of iron, chromium and aluminum. More preferably, the substrate is electrically heated.

[0077] Preferably, the catalyst of the present invention comprises a substrate (i) and a coating (ii).

[0078] It was a further object of the present invention to provide an exhaust gas treatment system capable of simultaneously performing selective catalytic reduction of NOx and decomposition and conversion of hydrocarbons, and of desulfurization by exothermic generation of temperature. Surprisingly, it has been found that the exhaust gas treatment system of the present invention is capable of simultaneously performing selective catalytic reduction of NOx and decomposition and conversion of hydrocarbons, and of desulfurization by exothermic generation of temperature.

[0079] Accordingly, the present invention relates to an exhaust gas treatment system for treating an exhaust gas stream exiting a diesel engine, said exhaust gas treatment system having an upstream end for introducing said exhaust gas stream into said exhaust gas treatment system, said exhaust gas treatment system comprising: (a) a first catalyst having an inlet end and an outlet end, said catalyst being a catalyst according to the present invention; (b) a second catalyst having an inlet end and an outlet end and comprising a coating disposed on a substrate, the coating comprising a platinum group metal supported on a non-zeolitic oxide material and further comprising one or more of vanadium oxide, tungsten oxide, and a zeolitic material comprising one or more of copper and iron; Including, The first catalyst according to (a) is a first catalyst of an exhaust gas treatment system downstream of an upstream end of the exhaust gas treatment system, an inlet end of the first catalyst being disposed upstream of an outlet end of the first catalyst; In the exhaust gas treatment system, a second catalyst according to (b) is disposed downstream of the first catalyst according to (a), with an inlet end of the second catalyst disposed upstream of an outlet end of the second catalyst.

[0080] Preferably, the outlet end of the first catalyst according to (a) is in fluid communication with the inlet end of the second catalyst according to (b), and no catalyst is disposed in the exhaust gas treatment system between the outlet end of the first catalyst according to (a) and the inlet end of the second catalyst according to (b) for treating the exhaust gas stream exiting the first catalyst.

[0081] Preferably, the platinum group metal of the coating of the second catalyst (b) is selected from the group consisting of platinum, palladium, rhodium, iridium and osmium, more preferably selected from the group consisting of platinum, palladium and rhodium, more preferably selected from the group consisting of platinum and palladium. More preferably, the platinum group metal of the second catalyst (b) is platinum.

[0082] Preferably, the coating of the second catalyst (b) has a concentration of 0.1 to 10 g / ft, calculated as elemental platinum group metal, more preferably elemental Pt. 3 , more preferably 0.2 to 5 g / ft 3 , more preferably 0.5 to 4 g / ft 3 , more preferably 1 to 3 g / ft 3 The catalyst comprises a platinum group metal, preferably Pt, at a loading in the range of 0.1 to 1.0 μg / g.

[0083] Preferably, the non-zeolitic oxide material of the coating of the second catalyst (b) comprises one or more of titania, zirconia, silica, alumina and ceria, more preferably one or more of titania, zirconia and alumina, more preferably one or more of titania and zirconia, more preferably titania, wherein the coating of the second catalyst (b) has a coating density of 0.05 to 1 g / in 3 , more preferably 0.1 to 0.5 g / in 3 The non-zeolitic oxide materials are included at loadings in the range of 0.1 to 1.0.

[0084] Preferably, 30 to 100 mass %, more preferably 50 to 99 mass %, more preferably 70 to 95 mass %, more preferably 80 to 92 mass % of the non-zeolitic oxide material is made of titania. More preferably, 5 to 15 mass %, more preferably 6 to 12 mass % of the non-zeolitic oxide material is made of silicon calculated as SiO2.

[0085] Preferably, the coating of the second catalyst (b) comprises a zeolitic material having a framework type selected from the group consisting of CHA, AEI, RTH, LEV, DDR, KFI, ERI, AFX, mixtures of two or more thereof, and mixed types of two or more thereof, more preferably selected from the group consisting of CHA, AEI, RTH, AFX, mixtures of two or more thereof, and mixed types of two or more thereof, more preferably selected from the group consisting of CHA and AEI. Preferably, the zeolitic material of the coating of the second catalyst (b) has framework type CHA.

[0086] The framework structure of the zeolite material coating the second catalyst (b) preferably consists of Si, Al and O in an amount of 95 to 100 mass%, more preferably 98 to 100 mass%, more preferably 99 to 100 mass%, more preferably 99.5 to 100 mass%.

[0087] The framework structure of the zeolite material preferably comprises P in an amount of up to 1% by mass, more preferably 0 to 0.5% by mass, and even more preferably 0 to 0.1% by mass.

[0088] Preferably, in the framework structure of the zeolitic material of the coating of the second catalyst (b), the molar ratio of Si to Al, calculated as molar SiO2:Al2O3, is more preferably in the range of 2:1 to 60:1, more preferably in the range of 2:1 to 50:1, more preferably in the range of 5:1 to 40:1, more preferably in the range of 10:1 to 35:1, more preferably in the range of 15:1 to 33:1, more preferably in the range of 15:1 to 20:1.

[0089] Preferably, the zeolitic material of the coating of the second catalyst (b), more preferably the zeolitic material of the coating of the second catalyst (b) having framework-type CHA, has an average crystallite size as determined by scanning electron microscopy of at least 0.1 micrometers, more preferably in the range of 0.1 to 3.0 micrometers, more preferably in the range of 0.3 to 1.5 micrometers, more preferably in the range of 0.4 to 1.0 micrometers.

[0090] Preferably, the coating of the second catalyst (b) is in the range of 1 to 6 g / in 3 More preferably, the range is 1.5 to 4 g / in 3 More preferably, in the range of 2 to 3 g / in 3 The zeolite material is included at loadings in the range of 0.1 to 1000 μg / kg.

[0091] Preferably, the zeolitic material contained in the coating of the second catalyst (b) comprises copper, wherein said coating comprises copper in an amount, calculated as CuO, based on the weight of the 8-ring porous zeolitic material contained in the coating of the second catalyst (b), more preferably in the range of 1 to 15% by weight, more preferably in the range of 1.25 to 10% by weight, more preferably in the range of 1.5 to 7% by weight, more preferably in the range of 2 to 6% by weight, more preferably in the range of 2.5 to 5.5% by weight, more preferably in the range of 4.5 to 5.25% by weight.

[0092] Preferably, the coating of the second catalyst (b) further comprises a metal oxide binder, wherein the metal oxide binder more preferably comprises one or more of zirconia, alumina, titania, silica, and mixed oxides comprising two or more of Zr, Al, Ti and Si, more preferably one or more of alumina and zirconia, more preferably zirconia.

[0093] Preferably, the coating of the second catalyst (b) comprises said metal oxide binder in an amount in the range of 1 to 8% by weight, more preferably in the range of 3 to 7% by weight, based on the weight of the zeolitic material containing one or more of copper and iron.

[0094] Preferably, the substrate of the second coating includes a plurality of passages defined by an inlet end, an outlet end, an axial length of the substrate extending from the inlet end to the outlet end, and an interior wall of the substrate extending therethrough, wherein, more preferably, the substrate is a flow-through substrate.

[0095] More preferably, the coating of the second catalyst (b) is - a bottom coat disposed on a surface of an interior wall of the substrate, said bottom coat comprising a zeolitic material comprising one or more of a platinum group metal, a non-zeolitic oxide material, copper and iron, and a metal oxide binder, preferably as defined above; and a topcoat disposed on said bottomcoat, said topcoat comprising a zeolitic material comprising one or more of copper and iron, and a metal oxide binder, preferably as defined above; Includes.

[0096] Preferably, the bottom coat extends over x% of the axial length of the substrate from the inlet end to the outlet end of the axial length of the substrate, where x is in the range 90-100, preferably in the range 95-100, more preferably in the range 99-100, and the top coat extends over y% of the axial length of the substrate from the inlet end to the outlet end of the axial length of the substrate, where y is in the range 90-x, more preferably y=x.

[0097] Alternatively, and preferably, the coating of the second catalyst (b) is a single coat.

[0098] In the context of the present invention, preferably, the substrate of the second catalyst (b) comprises a ceramic material, more preferably consists of a ceramic material, where the ceramic material more preferably comprises one or more of alumina, silica, silicate, aluminosilicate, more preferably cordierite or mullite, aluminotitanate, silicon carbide, zirconia, magnesia, more preferably spinel, and titania, more preferably one or more of silicon carbide and cordierite, more preferably cordierite, more preferably consists of the above. Alternatively, preferably, the substrate of the second catalyst (b) comprises a metal material, more preferably consists of a metal material.

[0099] There is no particular limitation on the substrate of the second catalyst (b) containing a metal material, more preferably consisting of a metal material, as long as it is a substrate suitable for the intended use of the second catalyst contained in the exhaust gas treatment system of the present invention. Preferably, the metal material contains oxygen and one or more of iron, chromium and aluminum, more preferably consists of oxygen and one or more of iron, chromium and aluminum. The substrate can further be electrically heated.

[0100] Preferably, a substrate having a first catalyst (a) disposed thereon and a substrate having a second catalyst (b) disposed thereon together form a single substrate, wherein the substrate has an inlet end and an outlet end, the inlet end being disposed upstream of the outlet end, a first catalyst coating is disposed on the substrate from the inlet end towards the outlet end of the substrate, and a second catalyst coating is disposed on the substrate from the outlet end towards the inlet end of the substrate, the first catalyst coating covering 25-75% of the substrate length and the second catalyst coating covering 25-75% of the substrate length. Preferably, the first catalyst coating covering 30-70%, more preferably 35-65%, more preferably 45-55% of the substrate length and the second catalyst coating covering 30-70%, more preferably 35-65%, more preferably 45-55% of the substrate length.

[0101] Preferably, the first catalyst coating and the second catalyst coating do not overlap.

[0102] A further object of the present invention was to provide a catalyst for the selective catalytic reduction of NOx, the oxidation of ammonia, and the decomposition and conversion of hydrocarbons, which exhibits improved catalytic properties and can be fully restored after sulfurization deactivation. Surprisingly, it has been found that the catalyst of the present invention for the selective catalytic reduction of NOx, the oxidation of ammonia, and the decomposition and conversion of hydrocarbons exhibits improved catalytic properties and can be fully restored after sulfurization deactivation.

[0103] Thus, the present invention provides - a substrate including an inlet end, an outlet end, a substrate axial length extending from the inlet end to the outlet end, and a plurality of passages defined by an interior wall of the substrate extending therethrough; - a first coating disposed on a surface of an interior wall of the substrate, the first coating comprising a platinum group metal supported on a non-zeolitic oxide material and further comprising one or more of vanadium oxide, tungsten oxide, and a zeolitic material comprising one or more of copper and iron; a second coating disposed on the first coating, the second coating comprising an 8-ring porous zeolite material comprising one or more of a platinum group metal, copper, and iron, and further comprising a 10 or more ring porous zeolite material; The present invention relates to catalysts for selective catalytic reduction of NOx, cracking and conversion of hydrocarbons, and oxidation of ammonia, including

[0104] Preferably, the first coating has a metal content of 0.1 to 20 g / ft, calculated as elemental platinum group metal, more preferably elemental Pt. 3 More preferably, the range is 1 to 15 g / ft 3 More preferably, the range is 3 to 10 g / ft 3 More preferably, it is in the range of 4 to 9 g / ft 3 Preferably, the catalyst comprises a platinum group metal, more preferably Pt, at a loading in the range of 1000 to 15000.

[0105] Preferably, the first coating comprises a zeolitic material having a framework type selected from the group consisting of CHA, AEI, RTH, LEV, DDR, KFI, ERI, AFX, mixtures of two or more thereof, and mixed types of two or more thereof, more preferably selected from the group consisting of CHA, AEI, RTH, AFX, mixtures of two or more thereof, and mixed types of two or more thereof, more preferably selected from the group consisting of CHA and AEI. More preferably, the zeolitic material of the first coating has framework type CHA.

[0106] The framework structure of the zeolite material of the first coating preferably consists of Si, Al and O in an amount of 95 to 100 mass%, more preferably 98 to 100 mass%, more preferably 99 to 100 mass%, and more preferably 99.5 to 100 mass%.

[0107] The framework structure of the zeolite material preferably comprises P in an amount of up to 1% by mass, more preferably 0 to 0.5% by mass, and even more preferably 0 to 0.1% by mass.

[0108] Preferably, in the framework structure of the zeolitic material of the first coating, the molar ratio of Si to Al, calculated as molar SiO2:Al2O3, is in the range of 2:1 to 60:1, more preferably in the range of 2:1 to 50:1, more preferably in the range of 5:1 to 40:1, more preferably in the range of 10:1 to 35:1, more preferably in the range of 15:1 to 33:1, more preferably in the range of 15:1 to 20:1.

[0109] Preferably, the zeolitic material of the first coating, more preferably the zeolitic material of the first coating having framework type CHA, has an average crystallite size as determined by scanning electron microscopy of at least 0.1 micrometers, more preferably in the range of 0.1 to 3.0 micrometers, more preferably in the range of 0.3 to 1.5 micrometers, more preferably in the range of 0.4 to 1.0 micrometers.

[0110] Preferably, the first coating has a density of 0.1 to 3 g / in 3More preferably, the range is 0.25 to 1 g / in 3 More preferably, the range is 0.3 to 0.75 g / in 3 The zeolite material is included at loadings in the range of 0.1 to 1000 μg / kg.

[0111] Preferably, the zeolitic material contained in the first coating comprises copper, wherein said coating comprises copper in an amount, calculated as CuO, based on the weight of the zeolitic material contained in the first coating, more preferably in the range of 1 to 15% by weight, more preferably in the range of 1.25 to 10% by weight, more preferably in the range of 1.5 to 7% by weight, more preferably in the range of 2 to 6% by weight, more preferably in the range of 2.5 to 5.5% by weight, more preferably in the range of 4.5 to 5.25% by weight.

[0112] Preferably, the non-zeolitic oxide material of the first coating comprises one or more of titania, zirconia, silica, alumina and ceria, more preferably one or more of titania, zirconia and alumina, more preferably one or more of titania and zirconia, more preferably titania.

[0113] Preferably, the first coating comprises said non-zeolitic oxide material in an amount in the range of 10 to 30 mass %, more preferably in the range of 15 to 25 mass %, based on the mass of the zeolitic material containing one or more of copper and iron contained in the first coating.

[0114] Preferably, 30 to 100% by mass, more preferably 50 to 99% by mass, more preferably 70 to 95% by mass, more preferably 80 to 92% by mass of the non-zeolitic oxide material of the first coating consists of titania.

[0115] Preferably, 5-15% by mass, more preferably 6-12% by mass, of the non-zeolitic oxide material consists of silicon calculated as SiO2.

[0116] Preferably, the first coating further comprises a metal oxide binder, more preferably comprising one or more of zirconia, alumina, titania, silica, and mixed oxides comprising two or more of Zr, Al, Ti and Si, more preferably one or more of alumina and zirconia, more preferably zirconia.

[0117] Preferably, the first coating comprises a metal oxide binder in an amount in the range of 1 to 8 mass %, more preferably in the range of 3 to 7 mass %, based on the mass of the copper and / or iron containing zeolitic material contained in the first coating.

[0118] Preferably, the first coating comprises - a bottom coat disposed on a surface of an interior wall of the substrate, said bottom coat comprising a platinum group metal, a non-zeolitic oxide material, and a zeolitic material comprising one or more of copper and iron, and preferably a metal oxide binder as defined above; and a topcoat disposed on said bottomcoat, said topcoat comprising a zeolitic material comprising one or more of copper and iron, and a metal oxide binder, preferably as defined above; Including, Here, the bottom coat preferably extends over x1% of the axial length of the substrate from the inlet end to the outlet end of the axial length of the substrate, where x1 is in the range of 90 to 100, more preferably 95 to 100, more preferably 99 to 100, and the top coat preferably extends over y1% of the axial length of the substrate from the inlet end to the outlet end of the axial length of the substrate, where y1 is in the range of 90 to x, more preferably y1=x1.

[0119] Alternatively, and preferably, the first coating is a single coat.

[0120] In the context of the present invention, preferably the first coating extends over 95-100%, preferably 98-100%, more preferably 99-100% of the axial length of the substrate.

[0121] Alternatively, preferably the first coating extends over 20-70%, preferably 40-60%, more preferably 45-55% of the axial length of the substrate.More preferably the first coating extends from the outlet end towards the inlet end of the substrate.

[0122] Preferably, 99 to 100% by mass, more preferably 99.5 to 100% by mass, more preferably 99.9 to 100% by mass of the first coating consists of a platinum group metal, a non-zeolitic oxide material, a zeolitic material containing one or more of copper and iron, and a metal oxide binder, preferably as defined above.

[0123] Preferably, the platinum group metal contained in the second coating is selected from the group consisting of palladium, platinum, rhodium, iridium and osmium, more preferably selected from the group consisting of palladium, platinum and rhodium, more preferably selected from the group consisting of palladium and platinum, more preferably the platinum group metal contained in the second coating is palladium.

[0124] Preferably, the second coating has a weight of from 2 to 100 g / ft, calculated as elemental platinum group metal. 3 More preferably, the range is 5 to 80 g / ft 3 More preferably, the range is 7 to 60 g / ft 3 More preferably, the range is 8 to 40 g / ft 3 More preferably, it is in the range of 10 to 30 g / ft 3 The platinum group metal is included in the carrier at a loading in the range of 0.1 to 1000 ppm.

[0125] Preferably, the second coating further comprises a non-zeolitic oxide material comprising one or more of alumina, zirconia, silica, titania and ceria, more preferably one or more of alumina, zirconia and silica, more preferably one or more of alumina and zirconia, more preferably alumina or zirconia.

[0126] Preferably, 30 to 100% by mass, more preferably 50 to 99% by mass, more preferably 70 to 95% by mass, more preferably 80 to 92% by mass of the non-zeolitic oxide material of the second coating consists of zirconia.

[0127] Preferably, 5-15% by weight, more preferably 6-12% by weight, of the non-zeolitic oxide material consists of lanthanum, calculated as La2O3.

[0128] Preferably, the 8-ring porous zeolitic material contained in the second coating has a framework type selected from the group consisting of CHA, AEI, RTH, LEV, DDR, KFI, ERI, AFX, mixtures of two or more thereof, and mixed types of two or more thereof, more preferably selected from the group consisting of CHA, AEI, RTH, AFX, mixtures of two or more thereof, and mixed types of two or more thereof, more preferably selected from the group consisting of CHA and AEI. More preferably, the 8-ring porous zeolitic material contained in the second coating has framework type CHA.

[0129] The framework structure of the 8-membered ring porous zeolite material contained in the second coating preferably consists of Si, Al and O at 95 to 100 mass%, more preferably 98 to 100 mass%, more preferably 99 to 100 mass%, and more preferably 99.5 to 100 mass%.

[0130] The framework structure of the zeolite material is preferably composed of P in a maximum of 1 mass %, more preferably 0 to 0.5 mass %, and more preferably 0 to 0.1 mass %.

[0131] Preferably, in the framework structure of the 8-membered ring porous zeolite material contained in the second coating, the molar ratio of Si to Al, calculated as molar SiO2:Al2O3, is in the range of 2:1 to 60:1, more preferably in the range of 2:1 to 50:1, more preferably in the range of 5:1 to 40:1, more preferably in the range of 10:1 to 35:1, more preferably in the range of 15:1 to 33:1, more preferably in the range of 15:1 to 20:1, or more preferably in the range of 25:1 to 33:1.

[0132] Preferably, the 8-ring porous zeolitic material contained in the second coating, more preferably the 8-ring porous zeolitic material contained in the second coating having framework type CHA, has an average crystallite size as determined by scanning electron microscopy of at least 0.1 micrometers, more preferably in the range of 0.1 to 3.0 micrometers, more preferably in the range of 0.3 to 1.5 micrometers, more preferably in the range of 0.4 to 1.0 micrometers.

[0133] Preferably, the second coating has a density of 0.1 to 3.0 g / in 3 More preferably, the range is 0.5 to 2.5 g / in 3 More preferably, the range is 0.7 to 2.2 g / in 3 More preferably, the range is 0.8 to 2.0 g / in 3 The zeolite material includes 8-ring porous material at loadings in the range of 100 to 2000 nm.

[0134] Preferably, the 8-ring porous zeolite material contained in the second coating comprises copper, wherein said coating comprises copper in an amount, calculated as CuO, based on the weight of the 8-ring porous zeolite material contained in the second coating, more preferably in the range of 1 to 15% by weight, more preferably in the range of 1.25 to 10% by weight, more preferably in the range of 1.5 to 7% by weight, more preferably in the range of 2 to 6% by weight, more preferably in the range of 2.5 to 5.5% by weight.

[0135] Preferably, the porous zeolite material with 10 or more ring members contained in the second coating is selected from the group consisting of FER, MFI, BEA, MWW, AFI, MOR, OFF, MFS, MTT, FAU, LTL, MEI, MOR, mixtures of two or more thereof, and mixed types of two or more thereof, preferably selected from the group consisting of FAU, FER, MFI, BEA, MWW, MOR, mixtures of two or more thereof, and mixed types of two or more thereof, more preferably a zeolite material having a framework type selected from the group consisting of FAU, FER, MFI and BEA. More preferably, the porous zeolite material with 10 or more ring members, more preferably 10 or 12 ring members, is a zeolite material having framework type FAU or FER or MFI or BEA.

[0136] The framework structure of the porous zeolite material having 10 or more membered rings is composed of Si, Al and O in an amount of preferably 95 to 100 mass%, more preferably 98 to 100 mass%, more preferably 99 to 100 mass%, and more preferably 99.5 to 100 mass%.

[0137] The framework structure of the zeolite material is preferably composed of P in a maximum of 1 mass %, more preferably 0 to 0.5 mass %, and more preferably 0 to 0.1 mass %.

[0138] Preferably, in the framework structure of the porous zeolite material having 10 or more ring members, the molar ratio of Si to Al calculated as molar SiO2:Al2O3 is more preferably in the range of 2:1 to 60:1, more preferably in the range of 3:1 to 40:1, more preferably in the range of 3:1 to 35:1.

[0139] Preferably, when the porous zeolite material having 10 or more ring members contained in the second coating is a zeolite material having a BEA framework, the molar ratio of Si to Al in the framework structure of the zeolite material, calculated as molar SiO2:Al2O3, is in the range of 4:1 to 20:1, more preferably in the range of 6:1 to 15:1, more preferably in the range of 8:1 to 12:1.

[0140] Alternatively, preferably, when the porous zeolite material having 10 or more ring members contained in the second coating is a zeolite material having a framework type FER, the molar ratio of Si to Al in the framework structure of the zeolite material, calculated as molar SiO2:Al2O3, is in the range of 10:1 to 30:1, more preferably in the range of 15:1 to 25:1, more preferably in the range of 18:1 to 22:1.

[0141] Alternatively, preferably, when the porous zeolite material having 10 or more ring members contained in the second coating is a zeolite material having a framework type FAU, the molar ratio of Si to Al in the framework structure of the zeolite material, calculated as molar SiO2:Al2O3, is in the range of 3:1 to 15:1, more preferably in the range of 4:1 to 10:1, and more preferably in the range of 4:1 to 8:1.

[0142] Alternatively, preferably, when the porous zeolite material having 10 or more membered rings contained in the second coating is a zeolite material having a framework MFI, the molar ratio of Si to Al in the framework structure of the zeolite material, calculated as molar SiO2:Al2O3, is in the range of 10:1 to 35:1, more preferably in the range of 20:1 to 32:1, more preferably in the range of 25:1 to 30:1.

[0143] In the context of the present invention, the 10 or more ring porous zeolitic material contained in the second coating preferably comprises one or more of iron, copper and rare earth elements, more preferably one or more of iron and rare earth elements. Alternatively, it is contemplated that the 10 or more ring porous zeolitic material contained in the second coating is in its H-form.

[0144] Preferably, the coating contains one or more of iron, copper and rare earth element components in an amount, calculated as the respective oxides, in the range of 1 to 20 mass %, more preferably in the range of 5 to 20 mass %, more preferably in the range of 2 to 8 mass %, or more preferably in the range of 10 to 20 mass %, based on the mass of the porous zeolite material having 10 or more ring members contained in the second coating.

[0145] Preferably, the porous zeolite material having 10 or more ring members contained in the second coating contains iron. More preferably, the second coating contains iron in an amount in the range of 2 to 8 mass %, more preferably in the range of 2.5 to 6 mass %, more preferably in the range of 3 to 5.5 mass %, calculated as Fe2O3, based on the mass of the porous zeolite material having 10 or more ring members contained in the second coating.

[0146] Alternatively, preferably, the 10 or more ring porous zeolite material comprised in the second coating comprises a rare earth element component, wherein the rare earth element component more preferably comprises one or more of La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Er, Y and Yb, more preferably comprises one or more of La, Ce, Pr, Nd, Sm, Eu, Y, Yb and Gd, more preferably comprises one or more of La and Ce.

[0147] More preferably, 60 to 100 mass %, and more preferably 80 to 100 mass % of the rare earth element component is La and / or Ce. In other words, it is preferable that La and / or Ce is the main element(s) in the rare earth element component contained in the second coating.

[0148] Preferably, when the porous zeolitic material having 10 or more ring members contained in the second coating comprises a rare earth element component, the second coating more preferably comprises the rare earth element component in an amount in the range of 10 to 20% by mass, more preferably in the range of 12 to 18% by mass, more preferably in the range of 14 to 17% by mass, calculated as the respective oxide(s), based on the mass of the porous zeolitic material having 10 or more ring members contained in coating (ii).

[0149] In the context of the present invention, preferably the second coating extends over 95-100%, more preferably 98-100%, more preferably 99-100% of the axial length of the substrate.

[0150] Preferably, the second coating comprises - an inlet coat comprising a platinum group metal and a porous zeolite material having 10 or more ring members; and - an outlet coat comprising a platinum group metal, a non-zeolitic oxide material, preferably as defined above, and an 8-ring porous zeolitic material containing one or more of copper and iron; and more preferably consisting of the above, wherein the inlet coat extends from the inlet end to the outlet end of the substrate over x2% of the axial length of the substrate, where x2 is in the range of 20 to 80, more preferably 30 to 60; The outlet coat extends from the outlet end towards the inlet end of the substrate over y2% of the axial length of the substrate, with y2 being in the range 20-80, more preferably 30-60.

[0151] Preferably, an inlet coat of the second coating is disposed on the first coating, and preferably, an outlet coat of the second coating is disposed on the first coating, where y2 is 100-x2.

[0152] Preferably, in the inlet coat of the second coating, the platinum group metal is supported on a porous zeolite material having 10 or more ring members, more preferably containing one or more of iron, copper and rare earth element components.

[0153] Preferably, the platinum group metal in the inlet coat of the second coating is palladium, and preferably the 10 or more ring porous zeolitic material in the inlet coat of the second coating is a zeolitic material having framework type BEA, more preferably wherein said zeolitic material comprises one or more of iron, copper and rare earth element components, more preferably one or more of iron and rare earth element components, more preferably iron.

[0154] Alternatively, preferably, the platinum group metal in the inlet coat of the second coating is palladium and the 10 or more ring porous zeolitic material in the inlet coat of the second coating is a zeolitic material having framework type FAU, more preferably, said zeolitic material comprising one or more of iron, copper and rare earth element components, more preferably one or more of iron and rare earth element components, more preferably a rare earth element component as defined above.

[0155] Alternatively, preferably, the platinum group metal in the inlet coat of the second coating is palladium and the 10 or more ring porous zeolitic material in the inlet coat of the second coating is a zeolitic material having framework type MFI, more preferably wherein said zeolitic material comprises one or more of iron, copper and rare earth element components, more preferably one or more of iron and rare earth element components, more preferably iron.

[0156] Preferably, 99 to 100% by mass, more preferably 99.5 to 100% by mass, more preferably 99.9 to 100% by mass of the inlet coat of the second coating is made of one or more of platinum group metals, porous zeolite materials having 10 or more ring members, and more preferably iron, copper and rare earth element components.

[0157] Preferably, the inlet coat of the second coating further comprises a non-zeolitic oxide material, more preferably a non-zeolitic oxide material as defined above, wherein the platinum group metal comprised in the inlet coat of the second coating is supported on said non-zeolitic oxide material, and the inlet coat of the second coating more preferably comprises the non-zeolitic oxide material in an amount more preferably in the range of 10 to 50 mass %, based on the mass of the inlet coat of the second coating.

[0158] Preferably, the platinum group metal in the inlet coat of the second coating is palladium, the non-zeolitic oxide material in the inlet coat of the second coating comprises zirconia or alumina, and the 10 or more ring porous zeolitic material in the inlet coat of the second coating is a zeolitic material having framework type BEA, more preferably wherein said zeolitic material comprises one or more of iron, copper and rare earth element components, more preferably one or more of iron and rare earth element components, more preferably iron.

[0159] Preferably, 99 to 100% by mass, more preferably 99.5 to 100% by mass, more preferably 99.9 to 100% by mass of the inlet coat of the second coating is made of one or more of platinum group metals, non-zeolitic oxide materials, porous zeolitic materials having 10 or more ring members, and more preferably iron, copper and rare earth element components.

[0160] Preferably, the inlet coat of the second coating has a weight of 5 to 40 g / ft, calculated as elemental platinum group metal. 3 More preferably, it is in the range of 10 to 35 g / ft 3 More preferably, it is in the range of 15 to 30 g / ft 3 The platinum group metal is included in the carrier at a loading in the range of 0.1 to 1000 ppm.

[0161] Preferably, the inlet coat of the second coating is 1 to 3 g / in 3 More preferably, in the range of 1.5 to 2.5 g / in 3 The zeolite material is included at loadings in the range of 0.1 to 1000 μg / kg.

[0162] Preferably, at most 0.1 wt. %, more preferably at most 0.01 wt. %, more preferably at most 0.001 wt. % of the inlet coat of the second coating consists of 8-ring porous zeolite material, in other words, preferably, the inlet coat of the second coating is substantially free of 8-ring porous zeolite material, more preferably, is substantially free of 8-ring porous zeolite material.

[0163] Preferably, the platinum group metal of the outlet coat of the second coating is supported on the non-zeolitic oxide material of the outlet coat of the second coating.

[0164] Preferably, the exit coat of the second coating is between 0.05 and 1 g / in 3 More preferably, the range is 0.1 to 0.5 g / in 3 The non-zeolitic oxide materials are included at loadings in the range of 0.1 to 1.0.

[0165] Preferably, the mass ratio of the 8-ring porous zeolite material of the outlet coat of the second coating to the non-zeolitic oxide material of the outlet coat of the second coating is in the range of 3:1 to 20:1, more preferably in the range of 5:1 to 15:1, more preferably in the range of 8:1 to 12:1.

[0166] Preferably, the molar ratio of Si to Al, calculated as molar SiO2:Al2O3, in the framework structure of the 8-ring porous zeolitic material of the outlet coat of the second coating is in the range of 15:1 to 33:1, more preferably in the range of 15:1 to 20:1. More preferably, said outlet coat of the second coating comprises copper, calculated as CuO, more preferably in the range of 2.5 to 5.5 wt%, more preferably in the range of 2.75 to 5.5 wt%, more preferably in the range of 4.5 to 5.25 wt%, based on the weight of the 8-ring porous zeolitic material contained in the outlet coat of the second coating.

[0167] Alternatively, preferably, the molar ratio of Si to Al, calculated as molar SiO2:Al2O3, in the framework structure of the 8-ring porous zeolitic material of the outlet coat of the second coating is in the range of 15:1 to 33:1, more preferably in the range of 25:1 to 33:1. More preferably, said outlet coat of the second coating comprises copper, calculated as CuO, more preferably in the range of 2.5 to 5.5% by weight, more preferably in the range of 2.75 to 5.5% by weight, more preferably in the range of 3 to 3.75% by weight, based on the weight of the 8-ring porous zeolitic material contained in the outlet coat of the second coating.

[0168] Preferably, the 8-ring porous zeolite material contained in the outlet coat of the second coating comprises copper, wherein said outlet coat of the second coating comprises copper in an amount, calculated as CuO, based on the weight of the 8-ring porous zeolite material contained in the outlet coat of the second coating, more preferably in the range of 2.5 to 5.5 mass %, more preferably in the range of 2.75 to 5.5 mass %, more preferably in the range of 3 to 3.75 mass %, or more preferably in the range of 4.5 to 5.25 mass %.

[0169] Preferably, the platinum group metal in the outlet coat of the second coating is palladium and the non-zeolitic oxide material of the outlet coat of the second coating comprises zirconia.

[0170] Preferably, the outlet coat of the second coating has a weight of 5 to 25 g / ft, calculated as elemental platinum group metal. 3 More preferably, it is in the range of 10 to 20 g / ft 3 The platinum group metal is included in the carrier at a loading in the range of 0.1 to 1000 ppm.

[0171] Preferably, the exit coat of the second coating is between 1 and 4 g / in 3 More preferably, in the range of 1.5 to 2.5 g / in 3 The zeolite material includes 8-ring porous material at loadings in the range of 100 to 2000 nm.

[0172] Preferably, the outlet coat of the second coating further comprises a metal oxide binder, wherein the metal oxide binder more preferably comprises one or more of zirconia, alumina, titania, silica, and mixed oxides comprising two or more of Zr, Al, Ti and Si, more preferably one or more of alumina and zirconia, more preferably zirconia.

[0173] Preferably, the outlet coat of the second coating comprises said metal oxide binder in an amount in the range of 1 to 8 mass %, more preferably in the range of 3 to 7 mass %, based on the mass of the 8-ring porous zeolite material containing one or more of copper and iron.

[0174] Preferably, 99 to 100% by mass, more preferably 99.5 to 100% by mass, more preferably 99.9 to 100% by mass of the outlet coat of the second coating consists of an 8-ring porous zeolite material containing one or more of a platinum group metal, a non-zeolitic oxide material, copper and iron, and more preferably a metal oxide binder as defined above.

[0175] Preferably, at most 0.1 wt. %, more preferably at most 0.01 wt. %, more preferably at most 0.001 wt. % of the outlet coat of the second coating consists of porous zeolite material with 10 or more ring members. In other words, preferably, the outlet coat of the second coating is substantially free of porous zeolite material with 10 or more ring members, more preferably free of porous zeolite material with 10 or more ring members.

[0176] Alternatively, and preferably, the second coating is a single coat.

[0177] Preferably, the non-zeolitic oxide material of the second coating comprises zirconia or alumina, where the second coating has a surface area of ​​preferably 0.05 to 1 g / in 3 , more preferably 0.1 to 0.5 g / in 3 The non-zeolitic oxide material is preferably present in a loading range of 0.1 to 1.0 μg / kg.

[0178] Preferably, in the framework structure of the 8-ring porous zeolite material of the second coating, the molar ratio of Si to Al, calculated as molar SiO2:Al2O3, is more preferably in the range of 15:1 to 20:1.

[0179] Preferably, the 8-ring porous zeolite material contained in the second coating comprises copper, wherein said coating comprises copper in an amount, calculated as CuO, based on the weight of the 8-ring porous zeolite material contained in the second coating, more preferably in the range of 2.5 to 5.5% by weight, more preferably in the range of 4.5 to 5.25% by weight.

[0180] Preferably, the mass ratio of the 8-ring porous zeolite material of the second coating to the non-zeolitic oxide material of the second coating is in the range of 2:1 to 15:1, more preferably in the range of 3:1 to 12:1, more preferably in the range of 5:1 to 9:1.

[0181] Preferably, the mass ratio of the 8-membered ring porous zeolite material of the second coating to the 10 or more membered ring porous zeolite material of the second coating is in the range of 2:1 to 15:1, more preferably in the range of 3:1 to 12:1, and more preferably in the range of 5:1 to 9:1.

[0182] Preferably, the 8-ring porous zeolitic material of the second coating has framework type CHA, and preferably the 10 or more ring porous zeolitic material of the second coating has framework type BEA and contains iron.

[0183] Alternatively, and preferably, the 8-ring porous zeolitic material of the second coating has framework type CHA and the 10 or more ring porous zeolitic material of the second coating has framework type FAU and comprises a rare earth component as defined above.

[0184] Alternatively, preferably, the 8-ring porous zeolitic material of the second coating has framework type CHA and the 10 or more ring porous zeolitic material of the second coating has framework type MFI and contains iron.

[0185] Alternatively, preferably, the 8-ring porous zeolitic material of the second coating has framework type CHA and the 10 or more ring porous zeolitic material of the second coating has framework type FER.

[0186] In the context of the present invention, preferably the second coating further comprises a metal oxide binder, wherein the metal oxide binder more preferably comprises one or more of zirconia, alumina, titania, silica and mixed oxides comprising two or more of Zr, Al, Ti and Si, more preferably one or more of alumina and zirconia, more preferably zirconia. More preferably, the second coating comprises said metal oxide binder in an amount in the range of 1-8 wt.%, more preferably in the range of 3-7 wt.%, based on the weight of the 8-ring porous zeolitic material comprising one or more of copper and iron.

[0187] Preferably, 99 to 100% by mass, more preferably 99.5 to 100% by mass, more preferably 99.9 to 100% by mass of the second coating consists of a 10 or more ring porous zeolite material optionally containing one or more of iron, copper and rare earth element components, an 8 ring porous zeolite material containing one or more of platinum group metals, copper and iron, more preferably a non-zeolitic oxide material as defined above, and more preferably a metal oxide binder as defined above.

[0188] Preferably, the substrate of the catalyst for selective catalytic reduction of NOx, decomposition and conversion of hydrocarbons, and oxidation of ammonia is preferably a flow-through substrate or a wall-flow filter substrate, more preferably a flow-through substrate. More preferably, the flow-through substrate comprises a ceramic material, more preferably consists of a ceramic material, where the ceramic material comprises more preferably one or more of alumina, silica, silicate, aluminosilicate, more preferably cordierite or mullite, aluminotitanate, silicon carbide, zirconia, magnesia, more preferably spinel, and titania, more preferably one or more of silicon carbide and cordierite, more preferably cordierite, more preferably consists of the above. Alternatively, more preferably, the flow-through substrate comprises a metal material, more preferably consists of a metal material. There is no particular restriction on the metal material, as long as the substrate is suitable for the intended use of the catalyst of the present invention for selective catalytic reduction of NOx, decomposition and conversion of hydrocarbons, and oxidation of ammonia. Preferably, the metallic material comprises oxygen and one or more of iron, chromium and aluminium, more preferably consists of oxygen and one or more of iron, chromium and aluminium. Preferably, the substrate is electrically heated.

[0189] Preferably, the catalyst of the present invention for the selective catalytic reduction of NOx, the cracking and conversion of hydrocarbons, and the oxidation of ammonia comprises a substrate, a first coating, and a second coating.

[0190] Furthermore, the present invention provides a method for producing a (1) providing an uncoated substrate, the substrate including an inlet end, an outlet end, an axial length of the substrate extending from the inlet end to the outlet end, and a plurality of passages defined by an interior wall of the substrate extending therethrough; (2) providing a slurry containing water, a platinum group metal precursor, preferably a palladium salt, a non-zeolite oxide material, an 8-ring porous zeolite material containing at least one of copper and iron, and a 10-ring or more porous zeolite material, and disposing the slurry on the inner wall surface of the substrate provided in step (1) over 90-100% of the axial length of the substrate from the inlet end to the outlet end; (3) calcining the slurry disposed on the substrate obtained in step (2) to obtain a catalyst for conversion of HC and selective catalytic reduction of NOx; The present invention relates to a method for preparing a catalyst for the decomposition and conversion of HC and the selective catalytic reduction of NOx, preferably a catalyst according to the present invention for the selective catalytic reduction of NOx and the decomposition and conversion of hydrocarbons, comprising:

[0191] Furthermore, the present invention provides a method for producing a (1') providing an uncoated substrate, the substrate including an inlet end, an outlet end, an axial length of the substrate extending from the inlet end to the outlet end, and a plurality of passages defined by an interior wall of the substrate extending therethrough; (2') providing a first slurry containing water, a platinum group metal precursor, preferably a palladium salt, and a porous zeolite material having 10 or more ring members, and disposing the slurry on the inner wall surface of the substrate provided in step (1') over x% of the axial length of the substrate from the inlet end to the outlet end of the substrate, where x is in the range of 20 to 80, preferably 30 to 60; (3') calcining the slurry disposed on the substrate obtained in step (2') to obtain a catalyst including an inlet coat; (4') providing a second slurry comprising water, a platinum group metal precursor, preferably a palladium salt, a non-zeolitic oxide material, and an 8-ring porous zeolite material comprising one or more of copper and iron, and disposing said slurry on the inner wall surface of the substrate provided in step (1') over y% of the axial length of the substrate from the outlet end toward the inlet end, where y is in the range of 20 to 80, preferably 30 to 60; (5') calcining the slurry disposed on the substrate obtained in step (4') to obtain a catalyst including an inlet coat and an outlet coat; The present invention relates to a method for preparing a catalyst for the decomposition and conversion of HC and the selective catalytic reduction of NOx, preferably a catalyst according to the present invention for the decomposition and conversion of HC and the selective catalytic reduction of NOx, comprising:

[0192] Furthermore, the present invention relates to the use of the catalyst according to the invention for the selective catalytic reduction of NOx and the decomposition and conversion of HC for simultaneously performing the selective catalytic reduction of NOx and the decomposition and conversion of HC.

[0193] Furthermore, the present invention provides a method for producing a (i) providing a gas stream comprising one or more of NOx, ammonia, nitric oxide, and hydrocarbons; (ii) contacting the gas stream provided in step (i) with a catalyst according to the present invention; The present invention relates to a method for simultaneously performing selective catalytic reduction of NOx and decomposition and conversion of HC, comprising:

[0194] Furthermore, the present invention relates to the use of the catalyst according to the invention for the decomposition and conversion of HC, the selective catalytic reduction of NOx and the oxidation of ammonia for simultaneously performing the selective catalytic reduction of NOx, the oxidation of ammonia and the decomposition and conversion of HC.

[0195] Furthermore, the present invention provides a method for producing a (i') providing a gas stream comprising one or more of NOx, ammonia, nitric oxide, and hydrocarbons; (ii') contacting the gas stream provided in step (i') with a catalyst according to the present invention; The present invention relates to a method for simultaneously performing selective catalytic reduction of NOx, oxidation of ammonia, and decomposition and conversion of HC, comprising:

[0196] Furthermore, the present invention provides a method for producing a A catalyst according to the invention for the decomposition and conversion of HC, selective catalytic reduction of NOx, and oxidation of ammonia, and One or more of the following: diesel oxidation catalyst, catalyzed soot filter, selective catalytic reduction (SCR) catalyst, SCR / AMOx catalyst The present invention relates to an exhaust gas treatment system comprising:

[0197] Preferably, the system comprises a catalyst according to the present invention for the decomposition and conversion of HC, selective catalytic reduction of NOx, and oxidation of ammonia, a diesel oxidation catalyst, a catalyzed soot filter, a selective catalytic reduction (SCR) catalyst, and a SCR / AMOx catalyst; Here, a catalyst according to the present invention is positioned upstream of a diesel oxidation catalyst and a catalyzed soot filter, the diesel oxidation catalyst is positioned upstream of an SCR catalyst, and the SCR catalyst is positioned upstream of an SCR / AMOx catalyst.

[0198] There are no particular limitations on the SCR catalyst used in the system, so long as it is effective in selectively catalytically reducing NOx. Any suitable SCR catalyst may be used. For example, a vanadium-containing SCR catalyst may be used.

[0199] Preferably, the diesel oxidation catalyst and the catalyzed soot filter are combined to obtain a diesel oxidation catalyst on a filter. The diesel oxidation catalyst more preferably comprises a diesel oxidation catalyst coating coated on a soot filter.

[0200] Preferably, the system further comprises a reductant injector, more preferably a urea injector, upstream of the SCR catalyst and downstream of the diesel oxidation catalyst.

[0201] Alternatively, preferably, the system comprises a catalyst according to the invention and a diesel oxidation catalyst, where the diesel oxidation catalyst is located upstream of the catalyst according to the invention.

[0202] Preferably, the system further comprises an HC injector upstream of the diesel oxidation catalyst, a reductant injector downstream of the diesel oxidation catalyst and upstream of the catalyst according to the invention, more preferably a urea injector.

[0203] Preferably the diesel oxidation catalyst comprises a platinum group metal supported on an oxide material, more preferably a non-zeolitic oxide material, where the diesel oxidation catalyst is more preferably a layered DOC or a mixed DOC.

[0204] Furthermore, the present invention provides a method for producing a (A) providing a gas stream comprising one or more of NOx, ammonia, nitric oxide, and hydrocarbons; (B) contacting the gas stream provided in step (A) with an exhaust gas treatment system according to the present invention; The present invention relates to a method for desulfurization by simultaneously performing selective catalytic reduction of NOx and decomposition and conversion of hydrocarbons, and generating heat by exothermic heating, including:

[0205] The present invention is illustrated by the combination of the following first set of embodiments and the embodiments resulting from the indicated dependencies and back references. This set of embodiments can be combined with the following second set of embodiments as shown below. In particular, in each instance where a range of embodiments is mentioned, it is to be noted that in the context of terms such as "the catalyst according to any one of the embodiments 1 to 4", all embodiments within this range are meant to be expressly disclosed to those skilled in the art, i.e., the expression of this term is understood by those skilled in the art to be synonymous with "the catalyst according to any one of the embodiments 1, 2, 3 and 4". Furthermore, it is to be expressly noted that the following set of embodiments represents a suitably constructed part of the description directed to the general and preferred aspects of the present invention, not the claims that determine the scope of protection.

[0206] 1. (i) a substrate including an inlet end, an outlet end, an axial length of the substrate extending from the inlet end to the outlet end, and a plurality of passages defined by an interior wall of the substrate extending therethrough; (ii) a coating disposed on a surface of an inner wall of a substrate, the coating comprising an 8-ring porous zeolite material comprising a platinum group metal and one or more of copper and iron, and further comprising a 10 or more ring porous zeolite material. Catalysts for selective catalytic reduction of NOx, and for the cracking and conversion of hydrocarbons, including

[0207] 2. The catalyst according to embodiment 1, wherein the platinum group metal contained in the coating (ii) is selected from the group consisting of palladium, platinum, rhodium, iridium and osmium, preferably selected from the group consisting of palladium, platinum and rhodium, more preferably selected from the group consisting of palladium and platinum, more preferably the platinum group metal contained in the coating (ii) is palladium.

[0208] 3. The coating has a metal content of 2 to 100 g / ft, calculated as elemental platinum group metal. 3 range, preferably 5 to 80 g / ft 3 More preferably, the range is 7 to 60 g / ft 3 More preferably, the range is 8 to 40 g / ft 3 More preferably, it is in the range of 10 to 30 g / ft 3 3. The catalyst of embodiment 1 or 2, comprising a platinum group metal at a loading in the range of

[0209] 4. The catalyst of any one of the preceding claims, wherein the coating (ii) further comprises a non-zeolitic oxide material comprising one or more of alumina, zirconia, silica, titania and ceria, preferably one or more of alumina, zirconia and silica, more preferably one or more of alumina and zirconia, more preferably alumina or zirconia.

[0210] 5. The non-zeolite oxide material is composed of 30 to 100% by mass, preferably 50 to 99% by mass, more preferably 70 to 95% by mass, and more preferably 80 to 92% by mass of zirconia; 5. The catalyst of embodiment 4, wherein preferably 5 to 15 wt. %, more preferably 6 to 12 wt. %, of the non-zeolitic oxide material consists of lanthanum, calculated as La2O3.

[0211] 6. The catalyst according to any one of the preceding claims, wherein the 8-ring porous zeolitic material contained in the coating (ii) is selected from the group consisting of CHA, AEI, RTH, LEV, DDR, KFI, ERI, AFX, mixtures of two or more thereof, and mixed types of two or more thereof, preferably selected from the group consisting of CHA, AEI, RTH, AFX, mixtures of two or more thereof, and mixed types of two or more thereof, more preferably selected from the group consisting of CHA and AEI, more preferably the 8-ring porous zeolitic material contained in the coating (ii) has framework type CHA.

[0212] 7. 95 to 100% by mass, preferably 98 to 100% by mass, more preferably 99 to 100% by mass, more preferably 99.5 to 100% by mass of the framework structure of the 8-membered ring porous zeolite material is composed of Si, Al and O, and in the framework structure of the zeolite material, the molar ratio of Si to Al calculated as molar SiO2:Al2O3 is more preferably in the range of 2:1 to 60:1, more preferably in the range of 2:1 to 50:1, more preferably in the range of 5:1 to 40:1, more preferably in the range of 10:1 to 35:1, more preferably in the range of 15:1 to 33:1, more preferably in the range of 15:1 to 20:1, or more preferably in the range of 25:1 to 33:1; 7. The catalyst according to any one of the preceding embodiments, wherein the framework structure of the zeolitic material consists of P, more preferably at most 1% by weight, more preferably 0-0.5% by weight, more preferably 0-0.1% by weight.

[0213] 8. The catalyst according to any one of the preceding claims, wherein the 8-ring porous zeolitic material, preferably having framework type CHA, contained in the coating (ii) has an average crystallite size, as determined by scanning electron microscopy, of at least 0.1 micrometers, preferably in the range of 0.1 to 3.0 micrometers, more preferably in the range of 0.3 to 1.5 micrometers, more preferably in the range of 0.4 to 1.0 micrometers.

[0214] 9. The coating (ii) has a coating thickness of 0.1 to 3.0 g / in 3 in the range of 0.5 to 2.5 g / in 3 More preferably, the range is 0.7 to 2.2 g / in 3 More preferably, the range is 0.8 to 2.0 g / in 3 9. The catalyst of any one of the preceding embodiments, comprising a zeolite material at a loading in the range of

[0215] 10. The catalyst according to any one of the preceding embodiments, wherein the 8-ring porous zeolitic material contained in the coating (ii) comprises copper, and the coating comprises copper in an amount, calculated as CuO, based on the weight of the 8-ring porous zeolitic material contained in the coating (ii), preferably in the range of 1 to 15% by weight, more preferably in the range of 1.25 to 10% by weight, more preferably in the range of 1.5 to 7% by weight, more preferably in the range of 2 to 6% by weight, more preferably in the range of 2.5 to 5.5% by weight.

[0216] 11. Catalyst according to any one of the preceding claims, wherein the porous zeolitic material with 10 or more ring members contained in the coating (ii) is selected from the group consisting of FER, MFI, BEA, MWW, AFI, MOR, OFF, MFS, MTT, FAU, LTL, MEI, MOR, mixtures of two or more thereof and mixed types of two or more thereof, preferably selected from the group consisting of FAU, FER, MFI, BEA, MWW, MOR, mixtures of two or more thereof and mixed types of two or more thereof, more preferably selected from the group consisting of FAU, FER, MFI and BEA, more preferably the porous zeolitic material with 10 or more ring members, preferably 10 or 12 ring members, is a zeolitic material with framework type FAU or FER or MFI or BEA.

[0217] 12. 95 to 100 mass%, preferably 98 to 100 mass%, more preferably 99 to 100 mass%, more preferably 99.5 to 100 mass% of the framework structure of the porous zeolite material having 10 or more ring members is composed of Si, Al and O, and in the framework structure of the zeolite material, the molar ratio of Si to Al calculated as molar SiO2:Al2O3 is more preferably in the range of 2:1 to 60:1, more preferably in the range of 3:1 to 40:1, more preferably in the range of 3:1 to 35:1; Catalyst according to any one of the preceding embodiments, wherein the framework structure of the zeolitic material consists of P, more preferably at most 1% by weight, more preferably 0-0.5% by weight, more preferably 0-0.1% by weight.

[0218] 13. The catalyst according to embodiment 12, wherein the porous zeolitic material having 10 or more ring members contained in the coating (ii) is a zeolitic material having a framework type BEA, and in the framework structure of the zeolitic material, the molar ratio of Si to Al calculated as molar SiO2:Al2O3 is in the range of 4:1 to 20:1, preferably in the range of 6:1 to 15:1, more preferably in the range of 8:1 to 12:1.

[0219] 14. The catalyst according to embodiment 12, wherein the porous zeolitic material having 10 or more ring members contained in the coating (ii) is a zeolitic material having a framework type FER, and in the framework structure of the zeolitic material, the molar ratio of Si to Al calculated as molar SiO2:Al2O3 is in the range of 10:1 to 30:1, preferably in the range of 15:1 to 25:1, more preferably in the range of 18:1 to 22:1.

[0220] 15. The porous zeolite material having 10 or more ring members contained in the coating (ii) is a zeolite material having a framework type FAU, and in the framework structure of the zeolite material, the molar ratio of Si to Al calculated as molar SiO2:Al2O3 is in the range of 3:1 to 15:1, preferably in the range of 4:1 to 10:1, more preferably in the range of 4:1 to 8:1; or Catalyst according to embodiment 12, wherein the porous zeolitic material having 10 or more ring members contained in the coating (ii) is a zeolitic material having a framework MFI, and in the framework structure of the zeolitic material, the molar ratio of Si to Al calculated as molar SiO2:Al2O3 is in the range of 10:1 to 35:1, preferably in the range of 20:1 to 32:1, more preferably in the range of 25:1 to 30:1.

[0221] 16. The porous zeolite material having 10 or more ring members contained in the coating (ii) comprises one or more of iron, copper and rare earth element components, preferably one or more of iron and rare earth element components; 15. The catalyst according to any one of the preceding embodiments, wherein the coating (ii) comprises one or more of iron, copper and rare earth element components, calculated as the respective oxides, in an amount preferably in the range of 1 to 20% by mass, more preferably in the range of 5 to 20% by mass, more preferably in the range of 10 to 20% by mass, based on the mass of the porous zeolite material having 10 or more ring members contained in the coating (ii).

[0222] 17. The zeolite material contains iron; or Catalyst according to embodiment 16, wherein the zeolitic material comprises a rare earth element component, the rare earth element component preferably comprising one or more of La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Er, Y and Yb, more preferably one or more of La, Ce, Pr, Nd, Sm, Eu, Y, Yb and Gd, more preferably one or more of La and Ce, and 60-100% by weight of the rare earth element component consists of La and / or Ce.

[0223] 18. The catalyst according to any one of the preceding embodiments, wherein the coating (ii) extends over 95-100%, preferably 98-100%, more preferably 99-100% of the axial length of the substrate.

[0224] 19. The coating according to (ii) (ii.1) an inlet coat comprising a platinum group metal and a porous zeolite material having 10 or more ring members; and (ii.2) an outlet coat comprising a platinum group metal, a non-zeolitic oxide material, more preferably a non-zeolitic oxide material as defined in embodiment 4 or 5, and an 8-ring porous zeolitic material comprising one or more of copper and iron; and more preferably consisting of the above, the inlet coat (ii.1) extends from the inlet end to the outlet end of the substrate according to (i) over x % of the axial length of the substrate, x being in the range 20 to 80, preferably 30 to 60; 19. The catalyst according to any one of the preceding embodiments, wherein the outlet coat (ii.2) extends from the outlet end towards the inlet end of the substrate according to (i) over y % of the axial length of the substrate, where y is in the range of 20 to 80, preferably 30 to 60.

[0225] 20. The inlet coat (ii.1) is disposed on the inner wall surface of the substrate (i); 20. The catalyst of embodiment 19, wherein the outlet coat (ii.2) is disposed on an inner wall surface of the substrate (i), and y is 100-x.

[0226] 21. The catalyst of embodiment 19 or 20, insofar as embodiment 19 is dependent on embodiment 16 or 17, wherein the platinum group metal is supported on the 10 or more ring porous zeolitic material containing one or more of iron, copper, and rare earth element components.

[0227] 22. The catalyst according to any one of embodiments 19 to 21, wherein the platinum group metal in the inlet coat (ii.1) is palladium and the 10 or more ring porous zeolitic material in the inlet coat (ii.1) is a zeolitic material having framework type BEA, the zeolitic material preferably comprising one or more of iron, copper and rare earth element components, more preferably one or more of iron and rare earth element components, more preferably iron.

[0228] 23. The catalyst according to any one of embodiments 19 to 21, wherein the platinum group metal in the inlet coat (ii.1) is palladium and the porous zeolitic material with 10 or more rings in the inlet coat (ii.1) is a zeolitic material with framework type FAU, the zeolitic material preferably comprising one or more of iron, copper and rare earth element components, more preferably one or more of iron and rare earth element components, more preferably a rare earth element component as defined in embodiment 17.

[0229] 24. The catalyst according to any one of embodiments 19 to 21, wherein the platinum group metal in the inlet coat (ii.1) is palladium and the 10 or more ring porous zeolitic material in the inlet coat (ii.1) is a zeolitic material having framework type MFI, the zeolitic material preferably comprising one or more of iron, copper and rare earth element components, more preferably one or more of iron and rare earth element components, more preferably iron.

[0230] 25. The catalyst according to any one of embodiments 19 to 24, wherein 99 to 100% by weight, preferably 99.5 to 100% by weight, more preferably 99.9 to 100% by weight, of the inlet coat (ii.1) consists of one or more of platinum group metals, porous zeolitic materials having 10 or more ring members, and preferably iron, copper and rare earth element components.

[0231] 26. The catalyst according to embodiment 19 or 20, wherein the inlet coat (ii.1) further comprises a non-zeolitic oxide material, preferably a non-zeolitic oxide material as defined in embodiment 4 or 5, wherein the platinum group metal contained in the inlet coat (ii.1) is supported on the non-zeolitic oxide material, and wherein the inlet coat (ii.1) comprises the non-zeolitic oxide material in an amount preferably in the range of 5 to 50% by weight, more preferably in the range of 10 to 50% by weight, based on the weight of the inlet coat (ii.1).

[0232] 27. The catalyst of embodiment 26, wherein the platinum group metal in the inlet coat (ii.1) is palladium, the non-zeolitic oxide material comprises zirconia or alumina, and the 10 or more ring porous zeolitic material in the inlet coat (ii.1) is a zeolitic material having framework type BEA, and the zeolitic material preferably comprises one or more of iron, copper and rare earth element components, more preferably one or more of iron and rare earth element components, more preferably iron.

[0233] 28. The catalyst of embodiment 26 or 27, wherein 99 to 100% by weight, preferably 99.5 to 100% by weight, more preferably 99.9 to 100% by weight, of the inlet coat (ii.1) consists of one or more of platinum group metals, non-zeolitic oxide materials, porous zeolitic materials having 10 or more ring members, and optionally iron, copper and rare earth element components.

[0234] 29. The inlet coat (ii.1) has a metal content of 5 to 40 g / ft, calculated as elemental platinum group metal. 3 range, preferably 10 to 35 g / ft 3 More preferably, it is in the range of 15 to 30 g / ft 3 29. The catalyst of any one of embodiments 19 to 28, comprising a platinum group metal at a loading in the range of

[0235] 30. The inlet coat (ii.1) has a thickness of 1 to 2 g / in 3 in the range of 1.1 to 1.5 g / in 330. The catalyst of any one of embodiments 19 to 29, comprising a zeolitic material at a loading in the range of

[0236] 31. The catalyst according to any one of embodiments 19 to 30, wherein at most 0.1% by weight, preferably at most 0.01% by weight, more preferably at most 0.001% by weight, of the inlet coat (ii.1) consists of 8-ring porous zeolitic material.

[0237] 32. The catalyst of any one of embodiments 19 to 31, wherein the platinum group metal of the outlet coat (ii.2) is supported on a non-zeolitic oxide material of the outlet coat (ii.2).

[0238] 33. The exit coat (ii.2) has a thickness of 0.05 to 1 g / in 3 in the range of 0.1 to 0.5 g / in 3 33. The catalyst of any one of embodiments 19 to 32, comprising a non-zeolitic oxide material at a loading in the range of

[0239] 34. The catalyst according to any one of embodiments 19 to 33, wherein the mass ratio of the 8-ring porous zeolitic material of the outlet coat (ii.2) to the non-zeolitic oxide material of the outlet coat (ii.2) is in the range of 3:1 to 20:1, preferably in the range of 5:1 to 15:1, more preferably in the range of 8:1 to 12:1.

[0240] 35. The catalyst according to any one of embodiments 19 to 34, wherein in the framework structure of the 8-ring porous zeolitic material of the outlet coat (ii.2), the molar ratio of Si to Al, calculated as molar SiO2:Al2O3, is in the range of 15:1 to 33:1, preferably in the range of 15:1 to 20:1, or preferably in the range of 25:1 to 33:1.

[0241] 36. The catalyst according to any one of embodiments 19 to 35, wherein the 8-ring porous zeolitic material contained in the outlet coat (ii.2) comprises copper, and the outlet coat (ii.2) comprises copper in an amount, calculated as CuO, based on the weight of the 8-ring porous zeolitic material contained in the outlet coat (ii.2), preferably in the range of 2.5 to 5.5% by weight, more preferably in the range of 2.75 to 5.5% by weight, more preferably in the range of 3 to 3.75% by weight, or more preferably in the range of 4.5 to 5.25% by weight.

[0242] 37. The catalyst of any one of embodiments 19 to 36, wherein the platinum group metal in the outlet coat (ii.2) is palladium and the non-zeolitic oxide material of the outlet coat (ii.2) comprises zirconia.

[0243] 38. The outlet coat (ii.2) has a metal content of 5 to 25 g / ft, calculated as elemental platinum group metal. 3 range, preferably 10 to 20 g / ft 3 38. The catalyst of any one of embodiments 19 to 37, comprising a platinum group metal at a loading in the range of

[0244] 39. The outlet coat (ii.2) has a thickness of 1 to 4 g / in 3 in the range of 1.5 to 2.5 g / in 3 39. The catalyst of any one of embodiments 19 to 38, comprising an 8-ring porous zeolitic material at a loading in the range of

[0245] 40. The outlet coat (ii.2) further comprises a metal oxide binder, the metal oxide binder preferably comprising one or more of zirconia, alumina, titania, silica, and mixed oxides comprising two or more of Zr, Al, Ti and Si, more preferably one or more of alumina and zirconia, more preferably zirconia; Catalyst according to any one of embodiments 19 to 39, wherein the outlet coat (ii.2) comprises the metal oxide binder in an amount in the range of 1 to 8% by weight, more preferably in the range of 3 to 7% by weight, based on the weight of the 8-ring porous zeolitic material comprising one or more of copper and iron.

[0246] 41. The catalyst according to any one of embodiments 19 to 40, wherein 99 to 100% by weight, preferably 99.5 to 100% by weight, more preferably 99.9 to 100% by weight, of the outlet coat (ii.2) consists of an 8-ring porous zeolitic material comprising one or more of a platinum group metal, a non-zeolitic oxide material, copper and iron, and a metal oxide binder, preferably as defined in embodiment 40.

[0247] 42. The catalyst according to any one of embodiments 19 to 41, wherein at most 0.1% by weight, preferably at most 0.01% by weight, more preferably at most 0.001% by weight, of the outlet coat (ii.2) consists of porous zeolitic material having 10 or more ring members.

[0248] 43. The catalyst according to any one of the preceding embodiments, wherein the coating (ii) is a single coat.

[0249] 44. The non-zeolitic oxide material of the coating (ii) comprises zirconia or alumina, and the coating (ii) has a coating density of preferably 0.05 to 1 g / in 3 , more preferably 0.1 to 0.5 g / in 3 44. The catalyst of embodiment 43, comprising the non-zeolitic oxide material at a loading in the range of

[0250] 45. The catalyst according to embodiment 43 or 44, wherein in the framework structure of the 8-ring porous zeolitic material of the coating (ii), the molar ratio of Si to Al, calculated as molar SiO2:Al2O3, is more preferably in the range of 15:1 to 20:1.

[0251] 46. ​​The catalyst according to any one of embodiments 43 to 45, wherein the 8-ring porous zeolitic material contained in the coating (ii) comprises copper, and the coating preferably comprises copper in an amount in the range of 2.5 to 5.5% by weight, more preferably in the range of 4.5 to 5.25% by weight, calculated as CuO, based on the weight of the 8-ring porous zeolitic material contained in the coating (ii).

[0252] 47. The catalyst according to any one of embodiments 43 to 46, wherein the mass ratio of the 8-ring porous zeolitic material of the coating (ii) to the non-zeolitic oxide material of the coating (ii) is in the range of 2:1 to 15:1, preferably in the range of 3:1 to 12:1, more preferably in the range of 5:1 to 9:1.

[0253] 48. The catalyst according to any one of embodiments 43 to 47, wherein the mass ratio of the 8-ring porous zeolite material of the coating (ii) to the 10 or more ring porous zeolite material of the coating (ii) is in the range of 2:1 to 15:1, preferably in the range of 3:1 to 12:1, more preferably in the range of 5:1 to 9:1.

[0254] 49. The catalyst according to any one of embodiments 43 to 48, wherein the 8-ring porous zeolitic material of coating (ii) has framework type CHA and the 10 or more ring porous zeolitic material of coating (ii) has framework type BEA and contains iron.

[0255] 50. The catalyst according to any one of embodiments 43 to 48, wherein the 8-ring porous zeolitic material of coating (ii) has framework type CHA and the 10 or more ring porous zeolitic material of coating (ii) has framework type FAU, and comprises a rare earth component as defined in embodiment 17.

[0256] 51. The catalyst according to any one of embodiments 43 to 48, wherein the 8-ring porous zeolitic material of coating (ii) has framework type CHA and the 10 or more ring porous zeolitic material of coating (ii) has framework type MFI and contains iron.

[0257] 52. The catalyst according to any one of embodiments 43 to 48, wherein the 8-ring porous zeolitic material of coating (ii) has framework type CHA and the 10 or more ring porous zeolitic material of coating (ii) has framework type FER.

[0258] 53. The coating (ii) further comprises a metal oxide binder, the metal oxide binder preferably comprising one or more of zirconia, alumina, titania, silica, and mixed oxides comprising two or more of Zr, Al, Ti and Si, more preferably one or more of alumina and zirconia, more preferably zirconia; 53. The catalyst of any one of embodiments 1 to 18 and 43 to 52, wherein the coating (ii) comprises the metal oxide binder in an amount preferably in the range of 1 to 8 wt.%, more preferably in the range of 3 to 7 wt.%, based on the weight of the 8-ring porous zeolitic material comprising one or more of copper and iron.

[0259] 54. The catalyst according to any one of the preceding embodiments, wherein 99 to 100%, preferably 99.5 to 100%, more preferably 99.9 to 100%, by weight, of the coating (ii) consists of a 10 or more ring porous zeolitic material optionally containing one or more of iron, copper and rare earth element components, an 8 ring porous zeolitic material containing one or more of a platinum group metal, copper and iron, preferably a non-zeolitic oxide material as defined in embodiment 4 or 5, and more preferably a metal oxide binder as defined in embodiment 40.

[0260] 55. The catalyst according to any one of the preceding embodiments, wherein the substrate (i) is a flow-through substrate or a wall-flow filter substrate, preferably a flow-through substrate.

[0261] 56. The catalyst of embodiment 55, wherein the flow-through substrate (i) comprises, and preferably consists of, a ceramic material, the ceramic material preferably comprising one or more of alumina, silica, silicate, aluminosilicate, preferably cordierite or mullite, aluminotitanate, silicon carbide, zirconia, magnesia, preferably spinel, and titania, more preferably one or more of silicon carbide and cordierite, more preferably cordierite, and more preferably consisting of the above.

[0262] 57. The catalyst of embodiment 55, wherein the flow-through substrate (i) comprises, and preferably consists of, a metal material, the metal material comprising oxygen and one or more of iron, chromium and aluminum, and more preferably consisting of oxygen and one or more of iron, chromium and aluminum.

[0263] 58. The catalyst of embodiment 57, wherein the substrate is electrically heated.

[0264] 59. The catalyst according to any one of the preceding embodiments, consisting of a substrate (i) and a coating (ii).

[0265] 60. An exhaust gas treatment system for treating an exhaust gas stream exiting a diesel engine, said exhaust gas treatment system having an upstream end for introducing said exhaust gas stream into said exhaust gas treatment system, said exhaust gas treatment system comprising: (a) a first catalyst having an inlet end and an outlet end, the catalyst being the catalyst of any one of the preceding embodiments; (b) a second catalyst having an inlet end and an outlet end and comprising a coating disposed on a substrate, the coating comprising a platinum group metal supported on a non-zeolitic oxide material and further comprising one or more of vanadium oxide, tungsten oxide, and a zeolitic material comprising one or more of copper and iron; Including, the first catalyst according to (a) is a first catalyst of the exhaust gas treatment system downstream of the upstream end of the exhaust gas treatment system, the inlet end of the first catalyst being disposed upstream of the outlet end of the first catalyst; In the exhaust gas treatment system, the second catalyst according to (b) is positioned downstream of the first catalyst according to (a), and the inlet end of the second catalyst is positioned upstream of the outlet end of the second catalyst.

[0266] 61. The exhaust gas treatment system of embodiment 60, wherein the outlet end of the first catalyst according to (a) is in fluid communication with the inlet end of the second catalyst according to (b), and no catalyst for treating the exhaust gas flow exiting the first catalyst is disposed in the exhaust gas treatment system between the outlet end of the first catalyst according to (a) and the inlet end of the second catalyst according to (b).

[0267] 62. The exhaust gas treatment system of embodiment 60 or 61, wherein the platinum group metal of the coating of the second catalyst (b) is selected from the group consisting of platinum, palladium, rhodium, iridium and osmium, preferably selected from the group consisting of platinum, palladium and rhodium, more preferably selected from the group consisting of platinum and palladium, and more preferably the platinum group metal of the second catalyst (b) is platinum.

[0268] 63. The coating of the second catalyst (b) has a metal content of 0.1 to 10 g / ft, calculated as elemental platinum group metal, preferably elemental Pt. 3 , preferably 0.2 to 5 g / ft 3 , more preferably 0.5 to 4 g / ft 3 , more preferably 1 to 3 g / ft 3 63. The exhaust gas treatment system of any one of embodiments 60 to 62, comprising a platinum group metal, preferably Pt, at a loading in the range of

[0269] 64. The non-zeolitic oxide material of the coating of the second catalyst (b) comprises one or more of titania, zirconia, silica, alumina and ceria, preferably one or more of titania, zirconia and alumina, more preferably one or more of titania and zirconia, more preferably titania, and the coating of the second catalyst (b) has a surface area of ​​0.05 to 1 g / in 3 , preferably 0.1 to 0.5 g / in 3 64. An exhaust gas treatment system according to any one of embodiments 60 to 63, comprising the non-zeolitic oxide material at a loading in the range of

[0270] 65. The non-zeolitic oxide material is composed of 30 to 100% by mass, preferably 50 to 99% by mass, more preferably 70 to 95% by mass, and more preferably 80 to 92% by mass of titania; 65. The exhaust gas treatment system of embodiment 64, wherein preferably 5 to 15 wt. %, more preferably 6 to 12 wt. %, of the non-zeolitic oxide material consists of silicon, calculated as SiO2.

[0271] 66. An exhaust gas treatment system according to any one of embodiments 60 to 65, wherein the coating of the second catalyst (b) comprises a zeolitic material having a framework type selected from the group consisting of CHA, AEI, RTH, LEV, DDR, KFI, ERI, AFX, mixtures of two or more thereof, and mixed types of two or more thereof, more preferably selected from the group consisting of CHA, AEI, RTH, AFX, mixtures of two or more thereof, and mixed types of two or more thereof, more preferably selected from the group consisting of CHA and AEI, and more preferably the zeolitic material of the coating of the second catalyst (b) has framework type CHA.

[0272] 67. 95-100% by mass, preferably 98-100% by mass, more preferably 99-100% by mass, more preferably 99.5-100% by mass of the framework structure of the zeolitic material of the coating of the second catalyst (b) is composed of Si, Al and O, and in the framework structure of the zeolitic material, the molar ratio of Si to Al, calculated as molar SiO2:Al2O3, is more preferably in the range of 2:1-60:1, more preferably in the range of 2:1-50:1, more preferably in the range of 5:1-40:1, more preferably in the range of 10:1-35:1, more preferably in the range of 15:1-33:1, more preferably in the range of 15:1-20:1; 67. An exhaust gas treatment system according to any one of embodiments 60 to 66, wherein the framework structure of the zeolitic material consists of P, more preferably at most 1%, more preferably 0-0.5%, more preferably 0-0.1% by weight.

[0273] 68. The exhaust gas treatment system of any one of embodiments 60 to 67, wherein the zeolitic material of the coating of the second catalyst (b), preferably the zeolitic material of the coating of the second catalyst (b) having framework-type CHA, has an average crystallite size determined by scanning electron microscopy of at least 0.1 micrometers, preferably in the range of 0.1 to 3.0 micrometers, more preferably in the range of 0.3 to 1.5 micrometers, more preferably in the range of 0.4 to 1.0 micrometers.

[0274] 69. The coating of the second catalyst (b) is 1 to 6 g / in 3 in the range of 1.5 to 4 g / in 3 More preferably, in the range of 2 to 3 g / in 3 69. The exhaust gas treatment system of any one of embodiments 60 to 68, comprising the zeolite material at a loading in the range of

[0275] 70. The exhaust gas treatment system of any one of embodiments 60 to 69, wherein the zeolitic material contained in the coating of the second catalyst (b) comprises copper, and the coating comprises copper in an amount, calculated as CuO, based on the weight of the 8-ring porous zeolitic material contained in the coating of the second catalyst (b), preferably in the range of 1 to 15% by weight, more preferably in the range of 1.25 to 10% by weight, more preferably in the range of 1.5 to 7% by weight, more preferably in the range of 2 to 6% by weight, more preferably in the range of 2.5 to 5.5% by weight, more preferably in the range of 4.5 to 5.25% by weight.

[0276] 71. The coating of the second catalyst (b) further comprises a metal oxide binder, the metal oxide binder preferably comprising one or more of zirconia, alumina, titania, silica, and mixed oxides comprising two or more of Zr, Al, Ti, and Si, more preferably one or more of alumina and zirconia, more preferably zirconia; 71. The exhaust gas treatment system of any one of embodiments 60 to 70, wherein the coating of the second catalyst (b) comprises the metal oxide binder in an amount preferably in the range of 1 to 8 wt.%, more preferably in the range of 3 to 7 wt.%, based on the weight of the zeolitic material comprising one or more of copper and iron.

[0277] 72. An exhaust gas treatment system as described in any one of embodiments 60 to 71, wherein the substrate of the second coating includes an inlet end, an outlet end, an axial length of the substrate extending from the inlet end to the outlet end, and a plurality of passages defined by an interior wall of the substrate extending therethrough, preferably the substrate is a flow-through substrate.

[0278] 73. The coating of the second catalyst (b) - a bottom coat disposed on a surface of an inner wall of the substrate, the bottom coat comprising a zeolitic material comprising one or more of a platinum group metal, a non-zeolitic oxide material, copper, and iron, and a metal oxide binder, preferably as defined in embodiment 62; and a topcoat disposed on the bottomcoat, the topcoat comprising a zeolitic material comprising one or more of copper and iron, and a metal oxide binder, preferably as defined in embodiment 71. 73. The exhaust gas treatment system of embodiment 72, comprising:

[0279] 74. The exhaust gas treatment system of embodiment 73, wherein the bottom coat extends over x% of the axial length of the substrate from the inlet end to the outlet end of the axial length of the substrate, where x is in the range of 90-100, preferably in the range of 95-100, more preferably in the range of 99-100, and the top coat extends over y% of the axial length of the substrate from the inlet end to the outlet end of the axial length of the substrate, where y is in the range of 90-x, more preferably y=x.

[0280] 75. The exhaust gas treatment system of any one of embodiments 60 to 72, wherein the coating of the second catalyst (b) is a single coat.

[0281] 76. The exhaust gas treatment system of any one of embodiments 60 to 75, wherein the substrate of the second catalyst (b) comprises, and preferably consists of, a ceramic material, and the ceramic material preferably comprises, and is preferably one or more of alumina, silica, silicate, aluminosilicate, preferably cordierite or mullite, aluminotitanate, silicon carbide, zirconia, magnesia, preferably spinel, and titania, more preferably one or more of silicon carbide and cordierite, more preferably cordierite, and more preferably consists of the above.

[0282] 77. An exhaust gas treatment system according to any one of embodiments 60 to 75, wherein the substrate of the second catalyst (b) comprises, and preferably consists of, a metal material, and the metal material preferably comprises oxygen and one or more of iron, chromium and aluminum, and more preferably consists of oxygen and one or more of iron, chromium and aluminum.

[0283] 78. The exhaust gas treatment system of embodiment 77, wherein the substrate is electrically heated.

[0284] 79. The exhaust gas treatment system of any one of embodiments 60 to 78, wherein the substrate of the first catalyst (a) on which the coating of the first catalyst is disposed and the substrate of the second catalyst (b) on which the coating of the second catalyst is disposed together form a single substrate, the single substrate including an inlet end and an outlet end, the inlet end being disposed upstream of the outlet end, the coating of the first catalyst being disposed on the single substrate from the inlet end towards the outlet end of the single substrate, the coating of the second catalyst being disposed on the single substrate from the outlet end towards the inlet end of the single substrate, the coating of the first catalyst covering 25-75% of the substrate length, and the coating of the second catalyst covering 25-75% of the substrate length.

[0285] 80. The exhaust gas treatment system of embodiment 79, wherein the first catalyst coating covers 30-70%, preferably 35-65%, more preferably 45-55% of the substrate length, and the second catalyst coating covers 30-70%, preferably 35-65%, more preferably 45-55% of the substrate length.

[0286] 81. The exhaust gas treatment system of embodiment 79 or 80, wherein the first catalyst coating and the second catalyst coating do not overlap.

[0287] 82. - A substrate including an inlet end, an outlet end, an axial length of the substrate extending from the inlet end to the outlet end, and a plurality of passages defined by an interior wall of the substrate extending therethrough; - a first coating disposed on a surface of an interior wall of the substrate, the first coating comprising a platinum group metal supported on a non-zeolitic oxide material and further comprising one or more of vanadium oxide, tungsten oxide, and a zeolitic material comprising one or more of copper and iron; a second coating disposed on the first coating, the second coating comprising an 8-ring porous zeolite material comprising one or more of a platinum group metal, copper, and iron, and further comprising a 10 or more ring porous zeolite material. Catalysts for selective catalytic reduction of NOx, cracking and conversion of hydrocarbons, and oxidation of ammonia, including

[0288] 83. The first coating has a metal content of 0.1 to 20 g / ft, calculated as elemental platinum group metal, preferably elemental Pt. 3 in the range of 1 to 15 g / ft 3 More preferably, the range is 3 to 10 g / ft 3 More preferably, it is in the range of 4 to 9 g / ft 3 83. The catalyst of embodiment 82, comprising a platinum group metal, preferably Pt, at a loading in the range of

[0289] 84. The catalyst of embodiment 82 or 83, wherein the first coating comprises a zeolitic material having a framework type selected from the group consisting of CHA, AEI, RTH, LEV, DDR, KFI, ERI, AFX, mixtures of two or more thereof, and mixed types of two or more thereof, more preferably selected from the group consisting of CHA, AEI, RTH, AFX, mixtures of two or more thereof, and mixed types of two or more thereof, more preferably selected from the group consisting of CHA and AEI, and more preferably the zeolitic material of the first coating has framework type CHA.

[0290] 85. 95-100% by mass, preferably 98-100% by mass, more preferably 99-100% by mass, more preferably 99.5-100% by mass of the framework structure of the zeolite material of the first coating is composed of Si, Al and O, and the molar ratio of Si to Al, calculated as molar SiO2:Al2O3, in the framework structure of the zeolite material is more preferably in the range of 2:1-60:1, more preferably in the range of 2:1-50:1, more preferably in the range of 5:1-40:1, more preferably in the range of 10:1-35:1, more preferably in the range of 15:1-33:1, more preferably in the range of 15:1-20:1; Catalyst according to any one of embodiments 82 to 84, wherein the framework structure of the zeolitic material consists of P, more preferably at most 1%, more preferably 0-0.5%, more preferably 0-0.1% by weight.

[0291] 86. The catalyst of any one of embodiments 82 to 85, wherein the zeolitic material of the first coating, preferably the zeolitic material of the first coating having framework type CHA, has an average crystallite size as determined by scanning electron microscopy of at least 0.1 micrometers, preferably in the range of 0.1 to 3.0 micrometers, more preferably in the range of 0.3 to 1.5 micrometers, more preferably in the range of 0.4 to 1.0 micrometers.

[0292] 87. The first coating has a thickness of 0.1 to 3 g / in 3 in the range of 0.25 to 1 g / in 3 More preferably, the range is 0.3 to 0.75 g / in 3 87. The catalyst of any one of embodiments 82 to 86, comprising a zeolitic material at a loading in the range of

[0293] 88. The catalyst of any one of embodiments 82 to 87, wherein the zeolitic material in the first coating comprises copper, and the coating comprises copper in an amount, calculated as CuO, based on the weight of the zeolitic material in the first coating, preferably in the range of 1 to 15%, more preferably in the range of 1.25 to 10%, more preferably in the range of 1.5 to 7%, more preferably in the range of 2 to 6%, more preferably in the range of 2.5 to 5.5%, more preferably in the range of 4.5 to 5.25% by weight.

[0294] 89. The catalyst of any one of embodiments 82 to 88, wherein the non-zeolitic oxide material of the first coating supporting a platinum group metal comprises one or more of titania, zirconia, silica, alumina and ceria, preferably one or more of titania, zirconia and alumina, more preferably one or more of titania and zirconia, more preferably titania, and the first coating comprises the non-zeolitic oxide material in an amount preferably in the range of 10 to 30% by weight, more preferably in the range of 15 to 25% by weight, based on the weight of the zeolitic material comprising one or more of copper and iron contained in the first coating.

[0295] 90. 30 to 100% by mass, preferably 50 to 99% by mass, more preferably 70 to 95% by mass, more preferably 80 to 92% by mass of the non-zeolitic oxide material of the first coating is titania; 90. The catalyst of embodiment 89, wherein preferably 5 to 15 wt.-%, more preferably 6 to 12 wt.-%, of the non-zeolitic oxide material consists of silicon calculated as SiO2.

[0296] 91. The first coating further comprises a metal oxide binder, the metal oxide binder preferably comprising one or more of zirconia, alumina, titania, silica, and mixed oxides comprising two or more of Zr, Al, Ti, and Si, more preferably one or more of alumina and zirconia, more preferably zirconia; 91. The catalyst of any one of embodiments 82 to 90, wherein the first coating comprises the metal oxide binder in an amount preferably in the range of 1 to 8 wt.%, more preferably in the range of 3 to 7 wt.%, based on the weight of the zeolitic material comprising one or more of copper and iron contained in the first coating.

[0297] 92. The first coating is - a bottom coat disposed on a surface of an inner wall of the substrate, the bottom coat comprising a platinum group metal, a non-zeolitic oxide material, and a zeolitic material comprising one or more of copper and iron, and a metal oxide binder, preferably as defined in embodiment 91; and a topcoat disposed on the bottomcoat, the topcoat comprising a zeolitic material comprising one or more of copper and iron, and a metal oxide binder, preferably as defined in embodiment 91. Including, Catalyst according to any one of embodiments 82 to 91, wherein the bottom coat preferably extends over x1% of the axial length of the substrate from the inlet end to the outlet end of the axial length of the substrate, where x1 is in the range of 90-100, more preferably in the range of 95-100, more preferably in the range of 99-100, and the top coat preferably extends over y1% of the axial length of the substrate from the inlet end to the outlet end of the axial length of the substrate, where y1 is in the range of 90-x, more preferably y1=x1.

[0298] 93. The catalyst of any one of embodiments 82 to 91, wherein the first coating is a single coat.

[0299] 94. The first coating extends over 95-100%, preferably 98-100%, more preferably 99-100% of the axial length of the substrate; or 94. The catalyst of any one of embodiments 82 to 93, wherein the first coating extends over 20 to 70%, preferably 40 to 60%, more preferably 45 to 55% of the axial length of the substrate; more preferably, the first coating extends from the outlet end towards the inlet end of the substrate.

[0300] 95. The catalyst of any one of embodiments 82 to 94, wherein 99 to 100%, preferably 99.5 to 100%, more preferably 99.9 to 100%, by weight, of the first coating consists of a zeolitic material comprising one or more of a platinum group metal, a non-zeolitic oxide material, copper and iron, and a metal oxide binder, preferably as defined in embodiment 91.

[0301] 96. The catalyst of any one of embodiments 82 to 95, wherein the platinum group metal comprised in the second coating is selected from the group consisting of palladium, platinum, rhodium, iridium and osmium, preferably selected from the group consisting of palladium, platinum and rhodium, more preferably selected from the group consisting of palladium and platinum, more preferably the platinum group metal comprised in the second coating is palladium.

[0302] 97. The second coating has a metal content of 2 to 100 g / ft, calculated as elemental platinum group metal. 3 range, preferably 5 to 80 g / ft 3 More preferably, the range is 7 to 60 g / ft 3 More preferably, the range is 8 to 40 g / ft 3 More preferably, it is in the range of 10 to 30 g / ft 3 The catalyst of any one of embodiments 82 to 96, comprising a platinum group metal at a loading in the range of

[0303] 98. The catalyst of any one of embodiments 82 to 97, wherein the second coating further comprises a non-zeolitic oxide material comprising one or more of alumina, zirconia, silica, titania, and ceria, preferably one or more of alumina, zirconia, and silica, more preferably one or more of alumina and zirconia, more preferably alumina or zirconia.

[0304] 99. 30 to 100% by mass, preferably 50 to 99% by mass, more preferably 70 to 95% by mass, more preferably 80 to 92% by mass of the non-zeolitic oxide material of the second coating is zirconia; Catalyst according to embodiment 98, wherein preferably 5 to 15% by weight, more preferably 6 to 12% by weight, of the non-zeolitic oxide material consists of lanthanum, calculated as La2O3.

[0305] 100. The catalyst according to any one of embodiments 82 to 99, wherein the 8-ring porous zeolitic material contained in the second coating is selected from the group consisting of CHA, AEI, RTH, LEV, DDR, KFI, ERI, AFX, mixtures of two or more thereof, and mixed types of two or more thereof, more preferably selected from the group consisting of CHA, AEI, RTH, AFX, mixtures of two or more thereof, and mixed types of two or more thereof, more preferably selected from the group consisting of CHA and AEI, and more preferably the 8-ring porous zeolitic material contained in the second coating has framework type CHA.

[0306] 101. 95 to 100 mass%, preferably 98 to 100 mass%, more preferably 99 to 100 mass%, more preferably 99.5 to 100 mass% of the framework structure of the 8-membered ring porous zeolite material contained in the second coating is composed of Si, Al and O, and in the framework structure of the zeolite material, the molar ratio of Si to Al calculated as molar SiO2:Al2O3 is more preferably in the range of 2:1 to 60:1, more preferably in the range of 2:1 to 50:1, more preferably in the range of 5:1 to 40:1, more preferably in the range of 10:1 to 35:1, more preferably in the range of 15:1 to 33:1, more preferably in the range of 15:1 to 20:1, or more preferably in the range of 25:1 to 33:1; 101. The catalyst according to any one of embodiments 82 to 100, wherein the framework structure of the zeolitic material consists of P, more preferably at most 1%, more preferably 0-0.5%, more preferably 0-0.1% by weight.

[0307] 102. The catalyst according to any one of embodiments 82 to 101, wherein the 8-ring porous zeolitic material contained in the second coating, preferably the 8-ring porous zeolitic material contained in the second coating having framework type CHA, has an average crystallite size determined by scanning electron microscopy of at least 0.1 micrometers, preferably in the range of 0.1 to 3.0 micrometers, more preferably in the range of 0.3 to 1.5 micrometers, more preferably in the range of 0.4 to 1.0 micrometers.

[0308] 103. The second coating has a thickness of 0.1 to 3.0 g / in 3 in the range of 0.5 to 2.5 g / in 3 More preferably, the range is 0.7 to 2.2 g / in 3 More preferably, the range is 0.8 to 2.0 g / in 3 103. The catalyst of any one of embodiments 82 to 102, comprising an 8-ring porous zeolitic material at a loading in the range of

[0309] 104. The catalyst according to any one of embodiments 82 to 103, wherein the 8-ring porous zeolite material contained in the second coating comprises copper, and the coating comprises copper in an amount, calculated as CuO, based on the weight of the 8-ring porous zeolite material contained in the second coating, preferably in the range of 1 to 15% by weight, more preferably in the range of 1.25 to 10% by weight, more preferably in the range of 1.5 to 7% by weight, more preferably in the range of 2 to 6% by weight, more preferably in the range of 2.5 to 5.5% by weight.

[0310] 105. The catalyst according to any one of embodiments 82 to 104, wherein the porous zeolitic material with 10 or more rings contained in the second coating is selected from the group consisting of FER, MFI, BEA, MWW, AFI, MOR, OFF, MFS, MTT, FAU, LTL, MEI, MOR, mixtures of two or more thereof, and mixed types of two or more thereof, preferably selected from the group consisting of FAU, FER, MFI, BEA, MWW, MOR, mixtures of two or more thereof, and mixed types of two or more thereof, more preferably selected from the group consisting of FAU, FER, MFI and BEA, more preferably the porous zeolitic material with 10 or more rings, preferably 10 or 12 rings, is a zeolitic material with framework type FAU or FER or MFI or BEA.

[0311] 106. 95 to 100 mass%, preferably 98 to 100 mass%, more preferably 99 to 100 mass%, more preferably 99.5 to 100 mass% of the framework structure of the porous zeolite material having 10 or more ring members is composed of Si, Al and O, and in the framework structure of the zeolite material, the molar ratio of Si to Al calculated as molar SiO2:Al2O3 is more preferably in the range of 2:1 to 60:1, more preferably in the range of 3:1 to 40:1, more preferably in the range of 3:1 to 35:1; 106. The catalyst according to any one of embodiments 82 to 105, wherein the framework structure of the zeolitic material consists of P, more preferably at most 1%, more preferably 0-0.5%, more preferably 0-0.1% by weight.

[0312] 107. The catalyst according to embodiment 106, wherein when the porous zeolite material having 10 or more ring members contained in the second coating is a zeolite material having a framework type BEA, the molar ratio of Si to Al in the framework structure of the zeolite material, calculated as molar SiO2:Al2O3, is in the range of 4:1 to 20:1, preferably in the range of 6:1 to 15:1, more preferably in the range of 8:1 to 12:1.

[0313] 108. The catalyst according to embodiment 106, wherein when the porous zeolite material having 10 or more ring members contained in the second coating is a zeolite material having a framework type FER, the molar ratio of Si to Al in the framework structure of the zeolite material, calculated as molar SiO2:Al2O3, is in the range of 10:1 to 30:1, preferably in the range of 15:1 to 25:1, more preferably in the range of 18:1 to 22:1.

[0314] 109. The catalyst according to embodiment 106, wherein when the porous zeolite material having 10 or more ring members contained in the second coating is a zeolite material having a framework type FAU, the molar ratio of Si to Al in the framework structure of the zeolite material, calculated as molar SiO2:Al2O3, is in the range of 3:1 to 15:1, preferably in the range of 4:1 to 10:1, more preferably in the range of 4:1 to 8:1.

[0315] 110. The catalyst according to embodiment 106, wherein when the porous zeolite material having 10 or more ring members contained in the second coating is a zeolite material having a framework type MFI, the molar ratio of Si to Al in the framework structure of the zeolite material, calculated as molar SiO2:Al2O3, is in the range of 10:1 to 35:1, preferably in the range of 20:1 to 32:1, more preferably in the range of 25:1 to 30:1.

[0316] 111. The 10 or more ring-membered porous zeolite material contained in the second coating comprises one or more of iron, copper, and rare earth element components, preferably one or more of iron and rare earth element components; 111. The catalyst according to any one of embodiments 82 to 110, wherein the coating comprises one or more of the iron, copper and rare earth element components, calculated as the respective oxides, in an amount preferably in the range of 1 to 20%, more preferably in the range of 2 to 19%, more preferably in the range of 3 to 18%, more preferably in the range of 3 to 6%, or more preferably in the range of 10 to 18% by weight, based on the weight of the 10 or more ring-membered porous zeolitic material contained in the second coating.

[0317] 112. The zeolite material contained in the second coating comprises iron; or 112. The catalyst of embodiment 111, wherein the zeolitic material in the second coating comprises a rare earth element component, the rare earth element component preferably comprising one or more of La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Er, Y, and Yb, more preferably one or more of La, Ce, Pr, Nd, Sm, Eu, Y, Yb, and Gd, more preferably one or more of La and Ce, and 60-100 wt.% of the rare earth element component consists of La and / or Ce.

[0318] 113. The catalyst of any one of embodiments 82 to 112, wherein the second coating extends over 95-100%, preferably 98-100%, more preferably 99-100% of the axial length of the substrate.

[0319] 114. The second coating is - an inlet coat comprising a platinum group metal and a porous zeolite material having 10 or more ring members; and an outlet coat comprising a platinum group metal, a non-zeolitic oxide material, preferably a non-zeolitic oxide material as defined in embodiment 98 or 99, and an 8-ring porous zeolitic material comprising one or more of copper and iron; and preferably consisting of the above, the inlet coat extends from the inlet end to the outlet end of the substrate over x2% of the axial length of the substrate, x2 being in the range of 20 to 80, preferably 30 to 60; 114. The catalyst of any one of embodiments 82 to 113, wherein the outlet coat extends over y2% of the axial length of the substrate from the outlet end towards the inlet end of the substrate, where y2 is in the range of 20 to 80, more preferably 30 to 60.

[0320] 115. The inlet coat of the second coating is disposed on the first coating; 115. The catalyst of embodiment 114, wherein the outlet coat of the second coating is disposed on the first coating, and y2 is 100-x2.

[0321] 116. The catalyst of embodiment 114 or 115, insofar as embodiment 114 is dependent on embodiment 112 or 113, wherein in the inlet coat of the second coating, the platinum group metal is supported on the 10 or more ring porous zeolite material, preferably containing one or more of iron, copper, and rare earth element components.

[0322] 117. The catalyst of any one of embodiments 114 to 116, wherein the platinum group metal in the inlet coat of the second coating is palladium, and the porous zeolitic material having 10 or more ring members in the inlet coat of the second coating is a zeolitic material having framework type BEA, and the zeolitic material preferably comprises one or more of iron, copper and rare earth element components, more preferably one or more of iron and rare earth element components, more preferably iron.

[0323] 118. The catalyst of any one of embodiments 114 to 116, wherein the platinum group metal in the inlet coat of the second coating is palladium, and the porous zeolitic material with 10 or more ring members in the inlet coat of the second coating is a zeolitic material having framework type FAU, and the zeolitic material preferably comprises one or more of iron, copper and rare earth element components, more preferably one or more of iron and rare earth element components, more preferably a rare earth element component as defined in embodiment 112.

[0324] 119. The catalyst of any one of embodiments 114 to 116, wherein the platinum group metal in the inlet coat of the second coating is palladium, and the porous zeolitic material with 10 or more ring members in the inlet coat of the second coating is a zeolitic material having framework type MFI, and the zeolitic material preferably comprises one or more of iron, copper and rare earth element components, more preferably one or more of iron and rare earth element components, more preferably iron.

[0325] 120. The catalyst of any one of embodiments 114 to 119, wherein 99 to 100% by weight, preferably 99.5 to 100% by weight, more preferably 99.9 to 100% by weight, of the inlet coat of the second coating consists of one or more of platinum group metals, porous zeolitic material having 10 or more ring members, and preferably iron, copper, and rare earth element components.

[0326] 121. The catalyst of embodiment 114 or 115, wherein the inlet coat of the second coating further comprises a non-zeolitic oxide material, preferably a non-zeolitic oxide material as defined in embodiment 4 or 5, the platinum group metal comprised in the inlet coat of the second coating is supported on the non-zeolitic oxide material, and the inlet coat of the second coating preferably comprises the non-zeolitic oxide material in an amount in the range of 10 to 50% by weight, based on the weight of the inlet coat of the second coating.

[0327] 122. The catalyst of embodiment 121, wherein the platinum group metal in the inlet coat of the second coating is palladium, the non-zeolitic oxide material in the inlet coat of the second coating comprises zirconia or alumina, and the porous zeolitic material with 10 or more rings in the inlet coat of the second coating is a zeolitic material having framework type BEA, and the zeolitic material preferably comprises one or more of iron, copper and rare earth element components, more preferably one or more of iron and rare earth element components, more preferably iron.

[0328] 123. The catalyst of embodiment 121 or 122, wherein 99 to 100%, preferably 99.5 to 100%, more preferably 99.9 to 100%, by weight, of the inlet coat of the second coating consists of one or more of platinum group metals, non-zeolitic oxide materials, porous zeolitic materials having 10 or more ring members, and preferably iron, copper, and rare earth element components.

[0329] 124. The inlet coat of the second coating has a metal content of 5 to 40 g / ft, calculated as elemental platinum group metal. 3 range, preferably 10 to 35 g / ft 3 More preferably, it is in the range of 15 to 30 g / ft 3 124. The catalyst of any one of embodiments 114 to 123, comprising a platinum group metal at a loading in the range of

[0330] 125. The inlet coat of the second coating has a thickness of 1 to 3 g / in 3 in the range of 1.5 to 2.5 g / in 3 125. The catalyst of any one of embodiments 114 to 124, comprising a zeolitic material at a loading in the range of

[0331] 126. The catalyst of any one of embodiments 114 to 125, wherein up to 0.1 wt.%, preferably up to 0.01 wt.%, more preferably up to 0.001 wt.% of the inlet coat of the second coating consists of 8-ring porous zeolite material.

[0332] 127. The catalyst of any one of embodiments 114 to 126, wherein the platinum group metal of the outlet coat of the second coating is supported on a non-zeolitic oxide material of the outlet coat of the second coating.

[0333] 128. The exit coat of the second coating has a thickness of 0.05 to 1 g / in 3 in the range of 0.1 to 0.5 g / in 3 The catalyst of any one of embodiments 114 to 127, comprising a non-zeolitic oxide material at a loading in the range of

[0334] 129. The catalyst of any one of embodiments 114 to 128, wherein the mass ratio of the 8-ring porous zeolite material of the outlet coat of the second coating to the non-zeolitic oxide material of the outlet coat of the second coating is in the range of 3:1 to 20:1, preferably in the range of 5:1 to 15:1, more preferably in the range of 8:1 to 12:1.

[0335] 130. The catalyst of any one of embodiments 114 to 129, wherein the molar ratio of Si to Al, calculated as molar SiO2:Al2O3, in the framework structure of the 8-ring porous zeolite material of the outlet coat of the second coating is in the range of 15:1 to 33:1, preferably in the range of 15:1 to 20:1, or preferably in the range of 25:1 to 33:1.

[0336] 131. The catalyst of any one of embodiments 114 to 130, wherein the 8-ring porous zeolitic material in the outlet coat of the second coating comprises copper, and the outlet coat of the second coating comprises copper in an amount, calculated as CuO, preferably in the range of 2.5 to 5.5 wt.%, more preferably in the range of 2.75 to 5.5 wt.%, more preferably in the range of 3 to 3.75 wt.%, or more preferably in the range of 4.5 to 5.25 wt.%, based on the weight of the 8-ring porous zeolitic material in the outlet coat of the second coating.

[0337] 132. The catalyst of any one of embodiments 114 to 131, wherein the platinum group metal in the outlet coat of the second coating is palladium, and the non-zeolitic oxide material of the outlet coat of the second coating comprises zirconia.

[0338] 133. The outlet coat of the second coating has a metal content of 5 to 25 g / ft, calculated as elemental platinum group metal. 3 range, preferably 10 to 20 g / ft 3 133. The catalyst of any one of embodiments 114 to 132, comprising a platinum group metal at a loading in the range of

[0339] 134. The exit coat of the second coating has a thickness of 1 to 4 g / in 3 in the range of 1.5 to 2.5 g / in 3 134. The catalyst of any one of embodiments 114 to 133, comprising an 8-ring porous zeolitic material at a loading in the range of

[0340] 135. The outlet coat of the second coating further comprises a metal oxide binder, the metal oxide binder preferably comprising one or more of zirconia, alumina, titania, silica, and mixed oxides comprising two or more of Zr, Al, Ti, and Si, more preferably one or more of alumina and zirconia, more preferably zirconia; 135. The catalyst of any one of embodiments 114 to 134, wherein the outlet coat of the second coating comprises the metal oxide binder in an amount preferably in the range of 1 to 8 wt.%, more preferably in the range of 3 to 7 wt.%, based on the weight of the 8-ring porous zeolitic material containing one or more of copper and iron.

[0341] 136. The catalyst of any one of embodiments 114 to 135, wherein 99 to 100%, preferably 99.5 to 100%, more preferably 99.9 to 100%, by weight, of the outlet coat of the second coating consists of an 8-ring porous zeolitic material comprising one or more of a platinum group metal, a non-zeolitic oxide material, copper, and iron, and a metal oxide binder, preferably as defined in embodiment 135.

[0342] 137. The catalyst of any one of embodiments 114 to 136, wherein up to 0.1 wt.%, preferably up to 0.01 wt.%, more preferably up to 0.001 wt.% of the outlet coat of the second coating consists of porous zeolitic material having 10 or more ring members.

[0343] 138. The catalyst of any one of embodiments 82 to 113, wherein the second coating is a single coat.

[0344] 139. The non-zeolitic oxide material of the second coating comprises zirconia or alumina, and the second coating has a thickness of preferably 0.05 to 1 g / in 3 , more preferably 0.1 to 0.5 g / in 3 139. The catalyst of embodiment 138, comprising the non-zeolitic oxide material at a loading in the range of

[0345] 140. The catalyst of embodiment 138 or 139, wherein in the framework structure of the 8-ring porous zeolitic material of the second coating, the molar ratio of Si to Al, calculated as molar SiO2:Al2O3, is more preferably in the range of 15:1 to 20:1.

[0346] 141. The catalyst of any one of embodiments 138 to 140, wherein the 8-ring porous zeolite material in the second coating comprises copper, and the coating comprises copper in an amount, calculated as CuO, preferably in the range of 2.5 to 5.5% by weight, more preferably in the range of 4.5 to 5.25% by weight, based on the weight of the 8-ring porous zeolite material in the second coating.

[0347] 142. The catalyst of any one of embodiments 138 to 141, wherein the mass ratio of the 8-ring porous zeolite material of the second coating to the non-zeolitic oxide material of the second coating is in the range of 2:1 to 15:1, preferably in the range of 3:1 to 12:1, more preferably in the range of 5:1 to 9:1.

[0348] 143. The catalyst of any one of embodiments 138 to 142, wherein the mass ratio of the 8-ring porous zeolite material of the second coating to the 10 or more ring porous zeolite material of the second coating is in the range of 2:1 to 15:1, preferably in the range of 3:1 to 12:1, more preferably in the range of 5:1 to 9:1.

[0349] 144. The catalyst of any one of embodiments 138 to 143, wherein the 8-ring porous zeolitic material of the second coating has framework type CHA and the 10 or more ring porous zeolitic material of the second coating has framework type BEA and contains iron.

[0350] 145. The catalyst of any one of embodiments 138 to 143, wherein the 8-ring porous zeolitic material of the second coating has framework type CHA and the 10 or more ring porous zeolitic material of the second coating has framework type FAU, and comprises a rare earth component as defined in embodiment 112.

[0351] 146. The catalyst of any one of embodiments 138 to 143, wherein the 8-ring porous zeolitic material of the second coating has framework type CHA and the 10 or more ring porous zeolitic material of the second coating has framework type MFI and contains iron.

[0352] 147. The catalyst of any one of embodiments 138 to 143, wherein the 8-ring porous zeolitic material of the second coating has framework type CHA and the 10 or more ring porous zeolitic material of the second coating has framework type FER.

[0353] 148. The second coating further comprises a metal oxide binder, the metal oxide binder preferably comprising one or more of zirconia, alumina, titania, silica, and mixed oxides comprising two or more of Zr, Al, Ti, and Si, more preferably one or more of alumina and zirconia, more preferably zirconia; 148. The catalyst of any one of embodiments 82 to 113 or 138 to 147, wherein the second coating comprises the metal oxide binder in an amount preferably in the range of 1 to 8 wt.%, more preferably in the range of 3 to 7 wt.%, based on the weight of the 8-ring porous zeolitic material containing one or more of copper and iron.

[0354] 149. The catalyst of any one of embodiments 82 to 148, wherein 99 to 100%, preferably 99.5 to 100%, more preferably 99.9 to 100%, by weight, of the second coating consists of a 10 or more ring porous zeolitic material optionally containing one or more of iron, copper, and rare earth element components, an 8 ring porous zeolitic material containing one or more of a platinum group metal, copper, and iron, preferably a non-zeolitic oxide material as defined in embodiment 98 or 99, and more preferably a metal oxide binder as defined in embodiment 148.

[0355] 150. The catalyst of any one of embodiments 82 to 149, wherein the substrate is a flow-through substrate or a wall-flow filter substrate, preferably a flow-through substrate.

[0356] 151. The catalyst of embodiment 150, wherein the flow-through substrate comprises, and preferably consists of, a ceramic material, the ceramic material preferably comprising one or more of alumina, silica, silicate, aluminosilicate, preferably cordierite or mullite, aluminotitanate, silicon carbide, zirconia, magnesia, preferably spinel, and titania, more preferably one or more of silicon carbide and cordierite, more preferably cordierite, and more preferably consisting of the above.

[0357] 152. The catalyst of embodiment 151, wherein the flow-through substrate comprises, and preferably consists of, a metal material, and the metal material preferably comprises oxygen and one or more of iron, chromium, and aluminum, and more preferably consists of oxygen and one or more of iron, chromium, and aluminum.

[0358] 153. The catalyst of embodiment 152, wherein the substrate is electrically heated.

[0359] 154. The catalyst of any one of embodiments 82 to 153, comprising the substrate, the first coating, and the second coating.

[0360] 155. (1) providing an uncoated substrate, the substrate including an inlet end, an outlet end, an axial length of the substrate extending from the inlet end to the outlet end, and a plurality of passages defined by an interior wall of the substrate extending therethrough; (2) providing a slurry containing water, a platinum group metal precursor, preferably a palladium salt, a non-zeolite oxide material, an 8-ring porous zeolite material containing at least one of copper and iron, and a 10-ring or more porous zeolite material, and disposing the slurry on the inner wall surface of the substrate provided in step (1) over 90-100% of the axial length of the substrate from the inlet end to the outlet end; (3) calcining the slurry disposed on the substrate obtained in step (2) to obtain a catalyst for conversion of HC and selective catalytic reduction of NOx; A method for preparing a catalyst for the decomposition and conversion of HC and selective catalytic reduction of NOx, preferably the catalyst according to any one of the preceding embodiments, comprising:

[0361] 156. (1') providing an uncoated substrate, the substrate including an inlet end, an outlet end, an axial length of the substrate extending from the inlet end to the outlet end, and a plurality of passages defined by an interior wall of the substrate extending therethrough; (2') providing a first slurry containing water, a platinum group metal precursor, preferably a palladium salt, and a porous zeolite material having 10 or more ring members, and disposing the slurry on the inner wall surface of the substrate provided in step (1') over x% of the axial length of the substrate from the inlet end to the outlet end of the substrate, where x is in the range of 20 to 80, preferably 30 to 60; (3') calcining the slurry disposed on the substrate obtained in step (2') to obtain a catalyst including an inlet coat; (4') providing a second slurry comprising water, a platinum group metal precursor, preferably a palladium salt, a non-zeolitic oxide material, and an 8-ring porous zeolite material comprising one or more of copper and iron, and disposing said slurry on the inner wall surface of the substrate provided in step (1') over y% of the axial length of the substrate from the outlet end toward the inlet end, where y is in the range of 20 to 80, preferably 30 to 60; (5') calcining the slurry disposed on the substrate obtained in step (4') to obtain a catalyst including an inlet coat and an outlet coat; A method for preparing a catalyst for the decomposition and conversion of HC and selective catalytic reduction of NOx, preferably a catalyst according to any one of embodiments 19 to 42, comprising:

[0362] 157. Use of the catalyst according to any one of embodiments 1 to 59 for selective catalytic reduction of NOx and decomposition and conversion of HC for simultaneous selective catalytic reduction of NOx and decomposition and conversion of HC.

[0363] 158. (i) providing a gas stream comprising one or more of NOx, ammonia, nitric oxide, and hydrocarbons; (ii) contacting the gas stream provided in step (i) with the catalyst of any one of the preceding embodiments. A method for simultaneously performing selective catalytic reduction of NOx and decomposition and conversion of HC, comprising:

[0364] 159. Use of the catalyst according to any one of embodiments 82 to 154 for the decomposition and conversion of HC, selective catalytic reduction of NOx, and oxidation of ammonia, for simultaneous selective catalytic reduction of NOx, oxidation of ammonia, and decomposition and conversion of HC.

[0365] 160. (i') providing a gas stream comprising one or more of NOx, ammonia, nitric oxide, and hydrocarbons; (ii') contacting the gas stream provided in step (i') with the catalyst of any one of embodiments 82 to 154. A method for simultaneously performing selective catalytic reduction of NOx, oxidation of ammonia, and decomposition and conversion of HC, comprising:

[0366] 161. A catalyst according to any one of embodiments 82 to 154 for the decomposition and conversion of HC, selective catalytic reduction of NOx, and oxidation of ammonia; and One or more of the following: diesel oxidation catalyst, catalyzed soot filter, selective catalytic reduction (SCR) catalyst, SCR / AMOx catalyst 1. An exhaust gas treatment system comprising:

[0367] 162. A catalyst according to any one of embodiments 82 to 154, including a diesel oxidation catalyst, a catalyzed soot filter, a selective catalytic reduction (SCR) catalyst, and an SCR / AMOx catalyst; The system of embodiment 161, wherein the catalyst of any one of embodiments 82 to 154 is disposed upstream of the diesel oxidation catalyst and the catalyzed soot filter, the diesel oxidation catalyst is disposed upstream of the SCR catalyst, and the SCR catalyst is disposed upstream of the SCR / AMOx catalyst.

[0368] 163. The system of embodiment 162, wherein the diesel oxidation catalyst and the catalyzed soot filter are combined.

[0369] 164. The system of embodiment 162 or 163, further comprising a urea injector upstream of the SCR catalyst and downstream of the diesel oxidation catalyst.

[0370] 165. A catalyst according to any one of embodiments 1 to 59 or any one of embodiments 82 to 154, and a diesel oxidation catalyst; The system of embodiment 161, wherein the diesel oxidation catalyst is disposed upstream of the catalyst of any one of embodiments 1 to 59 or any one of embodiments 82 to 154.

[0371] 166. The system of embodiment 165, further comprising an HC injector upstream of the diesel oxidation catalyst, and a urea injector downstream of the diesel oxidation catalyst and upstream of the catalyst of any one of embodiments 1 to 59 or any one of embodiments 82 to 154.

[0372] 167. The system of any one of embodiments 161 to 166, wherein the diesel oxidation catalyst comprises a platinum group metal supported on an oxide material, preferably a non-zeolitic oxide material, and the diesel oxidation catalyst is preferably a layered DOC or a mixed DOC.

[0373] 168. (A) providing a gas stream comprising one or more of NOx, ammonia, nitric oxide, and hydrocarbons; (B) contacting the gas stream provided in step (A) with the exhaust gas treatment system of any one of embodiments 60 to 81 or any one of embodiments 161 to 167. A method of desulfurization that simultaneously performs selective catalytic reduction of NOx and decomposition and conversion of hydrocarbons, generating heat through exothermic heat generation, including the use of a sintered gas.

[0374] In the context of the present invention, the term "inner wall surface" is understood, unless otherwise stated, as the "bare" or "uncovered" or "blank" surface of the wall, i.e. the surface of the wall in its untreated state consisting of the wall material, except for unavoidable impurities which may contaminate the surface.

[0375] Furthermore, in the context of the present invention, the term "X is one or more of A, B, and C" (where X is a given feature and each of A, B, and C represents a specific realization of that feature) is understood to disclose that X is either A, or B, or C, or A and B, or A and C, or B and C, or A and B and C. In this regard, it is noted that those skilled in the art can translate the above abstract terms into concrete examples, for example, when X is a chemical element and A, B, and C are specific elements such as Li, Na, and K, or when X is a temperature and A, B, and C are specific temperatures such as 10°C, 20°C, and 30°C. In this regard, it is further noted that those skilled in the art may extend the above terms to less specific realizations of said features, e.g., "X is one or more of A and B" discloses that X is either A, or B, or A and B, and, e.g., "X is one or more of A, B, C, and D" discloses that X is either A, or B, or C, or D, or A and B, or A and C, or A and D, or B and C, or B and D, or C and D, or A and B and C, or A and B and D, or B and C and D, or A and B and C and D.

[0376] Furthermore, in the context of the present invention, (g / in 3 or g / ft 3 The term "loading of a given component / coating" (in g / in) refers to the mass of said component / coating per volume of substrate, where the volume of the substrate is the cross-sectional volume of the substrate multiplied by the axial length of the substrate over which said component / coating is present. For example, a substrate that extends over x% of the axial length of the substrate and has a loading of X g / in 3 When referring to a loading of a first coating having a loading of 0.01 to 0.01, the loading is relative to the total substrate volume (in 3 This refers to X grams of first coating per x% of the total mass (expressed as x grams per x%).

[0377] In the context of the present invention, the term "porous zeolite material with 10 or more ring members" preferably means a porous zeolite material with 10 ring members, a porous zeolite material with 12 ring members or a porous zeolite material with 14 ring members, more preferably a porous zeolite material with 10 ring members or a porous zeolite material with 12 ring members.

[0378] The present invention is further illustrated by the following examples. EXAMPLES

[0379] Reference Example 1: Determination of Dv90 value Particle size distribution was measured by static light scattering using a Sympatec HELOS instrument, where the optical density of the samples was in the range of 5–10%.

[0380] Reference Example 2: Preparation of Cu-CHA zeolite The zeolitic material with Cu-containing framework type CHA used in the examples herein was prepared according to the teachings of US 8 293 199 B2, with particular reference to inventive example 2 in column 15, lines 26 to 52 of US 8 293 199 B2.

[0381] Reference Example 3: Measurement of BET specific surface area The BET specific surface area was determined according to DIN 66131 or DIN ISO 9277 with liquid nitrogen.

[0382] Reference Example 4: General coating method To coat a flow-through substrate with one or more coatings, the flow-through substrate was dipped vertically into a portion of a given mixture, preferably over a specific length of the substrate equal to the target length of the coating to be applied, and a vacuum was applied. In this way, the mixture was in contact with the walls of the substrate. The sample was left in the mixture for a period of time, typically 1-10 seconds. A vacuum was applied to draw the mixture into the substrate. The substrate was then removed from the mixture. The substrate was rotated on its axis so that the immersed side was now facing upwards, and the mixture, filled with high pressure air, was forced into the substrate.

[0383] Reference Example 5: Preparation of a catalyst not according to the present invention Zirconium-based oxide support (88% by mass ZrO2, 10% by mass La2O3, and 2% by mass HfO2, 67m 2 Incipient wetness impregnation of Pd into a ZrO2 oxide support (having a BET specific surface area of ​​100 nm / g, a Dv50 of 3 micrometers, and a Dv90 of 16 micrometers). First, the available pore volume of the oxide support was determined, and based on this value, a volume of diluted palladium salt solution was made equal to the available pore volume. This diluted solution was then added dropwise to the Zr-based oxide support over a period of 30 minutes with continuous stirring to obtain a wet material. The resulting material was then calcined in an oven at 590°C and cooled. After calcination, the resulting powder was mixed with distilled water to form an aqueous mixture with 40% solids, and the pH was adjusted to 3.75 with an organic acid. At this point, the slurry was milled until the particles of the Pd-impregnated ZrO2 mixture had a Dv90 of 10 micrometers. Separately, a Cu-CHA zeolite material (calculated as CuO based on the weight of Cu-CHA, Cu:3.25 wt.%, Dv90 of 25 micrometers, SiO2:Al2O3 molar ratio of 31:1, and ca. 625 m 2 Cu-CHA (having a BET specific surface area of ​​1000 μm / g) was added to deionized water to form a mixture. Further, a soluble zirconium solution (30 wt% ZrO2) was added as a binder to the mixture containing water and Cu-CHA. The pH was adjusted to 7. The solids content of the final mixture was 43 wt%.

[0384] At this point, the Pd-impregnated ZrO2 mixture was mixed into the Cu-CHA mixture and the pH was adjusted again to 7. The final mixture was mixed with the honeycomb flow-through monolith cordierite substrate (400 / (2.54) per square centimeter) 2 The substrate was then prepared for placement on a 10.5 in. diameter by 3 in. cylindrical substrate with a wall thickness of 0.10 mm (4 mils) and a cell of 0.10 mm (0.2 in.) diameter by 0.2 in. (3 in.) diameter. The substrate was coated once from the inlet end of the substrate towards the outlet end of the substrate and once from the outlet end of the substrate towards the inlet end of the substrate over the entire axial length of the substrate (3 in.) to achieve a target coating density of 2.4 g / in3 An inlet washcoat loading of 2.05 g / in was achieved. To dry the coated substrate, the substrate was placed in an oven at 90° C. for approximately 30 minutes. After drying, the coated substrate was calcined at 590° C. for 30 minutes. The final loading of coating in the catalyst after calcination was 2.05 g / in. 3 Cu-CHA, 0.24g / in 3 Zirconia / HfO3 / La2O3, 0.1g / in 3 of zirconia (binder), and 15g / ft 3 Pd loading of 2.4g / in 3 It was.

[0385] Reference Example 6: Preparation of a multifunctional catalyst not according to the present invention coating: Bottom Coat: Si-doped titania powder (10% by mass SiO2, 200 m 2 A platinum ammine solution was added to the uncoated honeycomb flow-through cordierite monolith substrate (BET specific surface area of ​​400 / (2.54) per square centimeter) using the coating method described in Example 4. The final Pt / Si titania had a Pt content of 0.46 wt.% based on the weight of the Si titania. This material was added to water and the slurry was milled as described in Example 1 until the resulting Dv90 was 10 micrometers. A zirconyl-acetate mixture (5.1 wt.% CuO and 18:1 SiO2:Al2O3 molar ratio) was added to the aqueous slurry of Cu-CHA zeolite material to achieve 5 wt.% ZrO2 after calcination based on the weight of the zeolite material. The Pt-containing slurry was added to the Cu-CHA slurry and stirred to produce the final slurry. This final slurry was then coated onto an uncoated honeycomb flow-through cordierite monolith substrate (400 / (2.54) per square centimeter) using the coating method described in Example 4. 2The bottom coat was applied over the entire length of a 10.5 inch diameter by 3 inch length cylindrical substrate with a 0.10 mm (4 mil) wall thickness, from the inlet side to the outlet side of the substrate. The coated substrate was then dried at 90° C. for about 30 minutes and calcined at 590° C. for about 30 minutes. The loading of the bottom coat after calcination was 1.67 g / in. 3 Cu-CHA loading, 0.08 g / in 3 ZrO2 loading, 0.25g / in 3 Si-titania loading of 2.5g / ft 3 PGM loading of about 2 g / in 3 It was.

[0386] Top coat: A zirconyl-acetate solution was added to an aqueous slurry of Cu-CHA zeolite material (5.1 wt.% CuO based on the weight of Cu-CHA, and 18:1 SiO2:Al2O3 molar ratio) to achieve 5 wt.% ZrO2 after calcination based on the weight of the zeolite material. The slurry was then placed over the entire length of a honeycomb cordierite monolith substrate coated with a first coating, from the inlet side to the outlet side of the substrate, and coated with a first coating using the coating method described in Reference Example 4. The coated substrate was then dried and calcined. The topcoat loading after calcination was 2.0 g / in 3 The final catalyst loading (bottom coat + top coat) in the calcined catalyst was about 2.5 g / in 3 It was.

[0387] Example 1: Preparation of a multifunctional catalyst according to the present invention coating: Exit Court: Zirconium-based oxide support (88% by mass ZrO2, 10% by mass La2O3, and 2% by mass HfO2, 67m 2Incipient wetness impregnation of Pd into a non-zeolitic oxide support (ZrO2 having a BET specific surface area of ​​100 nm / g, a Dv50 of 3 micrometers, and a Dv90 of 16 micrometers) was performed. First, the available pore volume of the non-zeolitic oxide support was determined, and based on this value, a volume of diluted palladium salt solution was made equal to the available pore volume. This diluted solution was then added dropwise to the Zr-based oxide support over a period of 30 minutes with continuous stirring to obtain a wet material. The resulting material was then calcined in an oven at 590°C and cooled. After calcination, the resulting powder was mixed with distilled water to form an aqueous mixture with 40% solids, and the pH was adjusted to 3.75 with an organic acid. At this point, the slurry was milled until the particles of the Pd-impregnated ZrO2 mixture had a Dv90 of 10 micrometers. Separately, a Cu-CHA zeolite material (calculated as CuO based on the weight of Cu-CHA, Cu:3.25 wt.%, Dv90 of 25 micrometers, SiO2:Al2O3 molar ratio of 31:1, and ca. 625 m 2 Cu-CHA (having a BET specific surface area of ​​1000 μm / g) was added to deionized water to form a mixture. Further, a soluble zirconium solution (30 wt% ZrO2) was added as a binder to the mixture containing water and Cu-CHA. The pH was adjusted to 7. The solids content of the final mixture was 43 wt%.

[0388] At this point, the Pd-impregnated ZrO2 mixture was mixed into the Cu-CHA mixture and the pH was adjusted again to 7. The final mixture was mixed with the honeycomb flow-through monolith cordierite substrate (400 / (2.54) per square centimeter) 2 The substrate was then prepared for placement on a cylindrical substrate (a 10.5 in. diameter by 3 in. length cylindrical substrate with a 0.10 mm (4 mil) wall thickness and a 10.5 in. diameter by 3 in. diameter cell). The substrate was coated over 50% (1.5 in.) of the axial length of the substrate from the exit end of the substrate toward the entrance end of the substrate, achieving a target coating density of 2.4 g / in 3An inlet washcoat loading of 2.05 g / in was achieved. To dry the coated substrate, the substrate was placed in an oven at 90° C. for approximately 30 minutes. After drying, the coated substrate was calcined at 590° C. for 30 minutes. The final loading of the outlet coat in the catalyst after calcination was 2.05 g / in. 3 Cu-CHA, 0.24g / in 3 Zirconia / HfO3 / La2O3, 0.1g / in 3 of zirconia (binder), and 15g / ft 3 Pd loading of 2.4g / in 3 It was.

[0389] Entrance Court: Separately, a zeolite material of the BEA structure type ion-exchanged with iron (Fe-BEA: 4.5% by weight Fe calculated as Fe2O3 based on the weight of Fe-BEA, 600m 2 Incipient wetness impregnation of Pd into Fe-BEA (BEA having a BET specific surface area of ​​0.01 μm / g and a SiO2:Al2O3 molar ratio of 10:1) was performed. First, the available pore volume of the zeolite was determined, and based on this value, a diluted palladium salt solution was made with a volume equal to the available pore volume. This diluted solution was then added dropwise to the Fe-BEA zeolite support over a period of 30 minutes with continuous stirring to obtain a wet material. The resulting material was then calcined in an oven at 590° C. and cooled. After calcination, the resulting powder was mixed with distilled water to form an aqueous mixture with 40% solids content and the pH was adjusted to 3.75 using an organic acid. At this point, the mixture was milled until the particles of the mixture had a Dv90 of 10 micrometers. The mixture was then placed over 50% (1.5 inches) of the axial length of the substrate coated with the first coating, from the inlet end of the substrate toward the outlet end of the substrate, using the coating method described in Reference Example 4. The coated substrate was then dried and calcined as the first coating. After firing, the loading of the inlet coat was 1.575 g / in 3 The final loading of the inlet coat in the catalyst after calcination was 1.43 g / in 3 Fe-BEA, 0.15g / in 3 of zirconia (binder), and 30g / ft3 Pd loading of 1.575 g / in 3 It was.

[0390] The final total catalyst loading in the catalyst (inlet coat + outlet coat) was 22.5 g / ft 3 with a total Pd loading of 1.99 g / in 3 It was.

[0391] Example 2: Preparation of a multifunctional catalyst according to the present invention Aluminum oxide (200m 2 Incipient wetness impregnation of Pd into an aluminum oxide support (having a BET specific surface area of ​​100 nm / g, a Dv50 of 3 micrometers, and a Dv90 of 16 micrometers) was performed. First, the available pore volume of the non-zeolitic oxide support was determined, and based on this value, a volume of diluted palladium salt solution was made equal to the available pore volume. This diluted solution was then added dropwise to the aluminum oxide support over a period of 30 minutes with continuous stirring to obtain a wet material. The resulting material was then calcined in an oven at 590°C and cooled. After calcination, the resulting powder was mixed with distilled water to form an aqueous mixture with 40% solids, and the pH was adjusted to 3.75 with an organic acid. At this point, the slurry was milled until the particles of the mixture had a Dv90 of 10 micrometers.

[0392] Separately, a Cu-CHA zeolite material (calculated as CuO based on the weight of Cu-CHA, Cu: 5.1 wt.%, Dv90 of 25 micrometers, SiO2:Al2O3 molar ratio of 18.5:1, and ca. 625 m 2 / g), and Fe (3.5 wt. % calculated as Fe2O3) ion-exchanged MFI zeolite material (375 m 2 A mixture of Fe-MFI and Cu-CHA (having a BET specific surface area of ​​0.01 μm / g and a SiO2:Al2O3 molar ratio of 27.5:1) was added to deionized water in a mass ratio of about 9:1 to form a mixture. Further, a soluble zirconium solution (30 wt% ZrO2) was added as a binder to the mixture containing water, Fe-MFI, and Cu-CHA. The pH was adjusted to 7. The solids content of the final mixture was 38 wt%.

[0393] At this point, the Pd-impregnated Al2O3 mixture was mixed into the Cu-CHA / Fe-MFI mixture and the pH was adjusted back to 7. The final mixture was mixed with the honeycomb flow-through monolith cordierite substrate (400 / (2.54) per square centimeter) 2 The mixture was then ready to be placed on a cylindrical substrate (10.5 in. diameter by 3 in. length, with a cell of 0.10 mm (4 mils) wall thickness). The substrate was coated with the final mixture according to the coating method defined in Example 4. A target of 2.4 g / in 3 To achieve a washcoat loading of 1.8 g / in, the substrate was coated once over its entire length from the exit end to the inlet end of the substrate, with drying and calcination steps following the coating step. To dry the coated substrate, the substrate was placed in an oven at 90° C. for approximately 30 minutes. After drying, the coated substrate was calcined at 590° C. for 30 minutes. The final loading of coating in the catalyst after calcination was 1.8 g / in. 3 Cu-CHA, 0.25g / in 3 Fe-MFI, 0.25g / in 3 of Al2O3, 0.1g / in 3 of zirconia (binder), and 15g / ft 3 Pd loading of 2.4g / in 3 It was.

[0394] Example 3: Preparation of a multifunctional catalyst according to the present invention Aluminum oxide (200m 2Incipient wetness impregnation of Pd into an aluminum oxide support (having a BET specific surface area of ​​100 nm / g, a Dv50 of 3 micrometers, and a Dv90 of 16 micrometers) was performed. First, the available pore volume of the non-zeolitic oxide support was determined, and based on this value, a volume of diluted palladium salt solution was made equal to the available pore volume. This diluted solution was then added dropwise to the aluminum oxide support over a period of 30 minutes with continuous stirring to obtain a wet material. The resulting material was then calcined in an oven at 590°C and cooled. After calcination, the resulting powder was mixed with distilled water to form an aqueous mixture with 40% solids, and the pH was adjusted to 3.75 with an organic acid. At this point, the slurry was milled until the particles of the mixture had a Dv90 of 10 micrometers.

[0395] Separately, a Cu-CHA zeolite material (calculated as CuO based on the weight of Cu-CHA, Cu: 5.1 wt.%, Dv90 of 25 micrometers, SiO2:Al2O3 molar ratio of 18.5:1, and ca. 625 m 2 / g), and rare earth (RE) metal-exchanged zeolite Y (FAU framework type) (RE (mainly containing La and Ce): ca. 16 wt.%, calculated as Re2O3 based on the mass of RE-Y, 700 m 2 RE-Zeolite Y (having a BET specific surface area of ​​1000 μg / g and a SiO2:Al2O3 molar ratio of 5:1) was added to deionized water in a mass ratio of about 7:1 to form a mixture. Further, a soluble zirconium solution (30 wt% ZrO2) was added as a binder to the mixture containing water, RE-Zeolite Y, and Cu-CHA. The pH was adjusted to 7. The solids content of the final mixture was 38 wt%.

[0396] At this point, the Pd-impregnated Al2O3 mixture was mixed into the Cu-CHA / RE-Zeolite Y mixture and the pH was adjusted back to 7. The final mixture was mixed with the honeycomb flow-through monolith cordierite substrate (400 / (2.54) per square centimeter) 2The mixture was then ready to be placed on a cylindrical substrate (10.5 in. diameter by 3 in. length, with a cell of 0.10 mm (4 mils) wall thickness). The substrate was coated with the final mixture according to the coating method defined in General Coating Methods. A target coating density of 2.4 g / in 3 To achieve a washcoat loading of 1.8 g / in, the substrate was coated once over its entire length from the exit end to the inlet end of the substrate, with drying and calcination steps following the coating step. To dry the coated substrate, the substrate was placed in an oven at 90° C. for approximately 30 minutes. After drying, the coated substrate was calcined at 590° C. for 30 minutes. The final loading of coating in the catalyst after calcination was 1.8 g / in. 3 Cu-CHA, 0.25g / in 3 RE-Zeolite Y, 0.25g / in 3 of Al2O3, 0.1g / in 3 of zirconia (binder), and 15g / ft 3 Pd loading of 2.4g / in 3 It was.

[0397] Example 4: Preparation of an exhaust gas treatment system according to the present invention An exhaust gas treatment system according to the present invention was prepared by combining the catalyst of Example 1 (Catalyst 1) and the catalyst of Reference Example 6 (Catalyst 2), where the catalyst of Reference Example 6 was located downstream of the catalyst of Example 1.

[0398] Comparative Example 1: Preparation of an Exhaust Gas Treatment System Not According to the Invention An exhaust gas treatment system not according to the present invention was prepared by combining the catalyst of Reference Example 5 (Catalyst 1) and the catalyst of Reference Example 6 (Catalyst 2), where the catalyst of Reference Example 6 was positioned downstream of the catalyst of Reference Example 5.

[0399] Example 5: Testing of the exhaust gas treatment systems of Example 4 and Comparative Example 1 Steady state points were performed to test two different systems for HC oxidation capacity. Tests were performed downstream of a heavy duty diesel engine. Test conditions are shown in Figures 1-3. Catalyst 1 inlet temperatures were 305°C, 325°C and 350°C, with a target catalyst outlet temperature of 450°C. The temperatures downstream of catalyst 1 and downstream of catalyst 2 were measured in both systems. The results are shown in Figures 4 and 6 (Comparative Example 1) and Figures 5 and 7 (Inventive Example 4).

[0400] As can be seen from Figures 4 and 5, the targeted catalyst outlet temperature of 450°C was only achieved in the system according to the invention, which is able to achieve a higher heat release compared to the comparative system. Furthermore, with respect to Figures 6 and 7, which show the HC slip at the outlet end of catalyst 1 and catalyst 2 of the tested systems, it is noted that when full heat release is achieved (450°C), the HC slip is very low in the system according to the invention.

[0401] Example 6: Preparation of a multifunctional catalyst according to the present invention It has ammonium-form skeletal FER and is 400m 2 Incipient wetness impregnation of Pd into a zeolite material having a BET specific surface area of ​​1000 nm / g and SiO2:Al2O3 of 20:1. First, the available pore volume of the zeolite was determined, and based on this value, a volume of diluted palladium salt solution was made equal to the available pore volume. This diluted solution was then added dropwise to the FER zeolite material support over a period of 30 minutes with continuous stirring to obtain a wet material. The resulting material was then calcined in an oven at 590°C and cooled. After calcination, the resulting powder was mixed with distilled water to form an aqueous mixture with 40% solids, and the pH was adjusted to 3.75 with an organic acid. At this point, the slurry was milled until the particles of the mixture had a Dv90 of 10 micrometers. Separately, a Cu-CHA zeolite material (calculated as CuO based on the weight of Cu-CHA, Cu: 5.1 wt.%, Dv90 of 25 micrometers, SiO2:Al2O3 molar ratio of 18.5:1, and ca. 625 m 2Cu-CHA (having a BET specific surface area of ​​1000 μm / g) was added to deionized water to form a mixture. Further, a soluble zirconium solution (30 wt% ZrO2) was added as a binder to the mixture containing water and Cu-CHA. The pH was adjusted to 7. The solids content of the final mixture was 38 wt%.

[0402] At this point, the Pd-impregnated FER mixture was mixed into the Cu-CHA mixture and the pH was adjusted back to 7. The final mixture was then mixed with the honeycomb flow-through monolith cordierite substrate (400 / (2.54) per square centimeter) 2 The mixture was then ready to be placed on a cylindrical substrate (10.5 in. diameter by 3 in. length, with a cell of 0.10 mm (4 mils) wall thickness). The substrate was coated with the final mixture according to the coating method defined in Example 4. A target of 2.4 g / in 3 To achieve a washcoat loading of 2.05 g / in, the substrate was coated once over its entire length from the exit end to the inlet end of the substrate, with drying and calcination steps following the coating step. To dry the coated substrate, the substrate was placed in an oven at 90° C. for approximately 30 minutes. After drying, the coated substrate was calcined at 590° C. for 30 minutes. The final loading of coating in the catalyst after calcination was 2.05 g / in. 3 Cu-CHA, 0.25g / in 3 FER, 0.1g / in 3 of zirconia (binder), and 15g / ft 3 Pd loading of 2.4g / in 3 It was.

[0403] Example 7: Preparation of a multifunctional catalyst according to the present invention Zeolitic material with framework type BEA ion-exchanged with iron (Fe: 4.5 wt%, calculated as Fe2O3 based on the mass of Fe-BEA, 600 m 2Incipient wetness impregnation of Pd into Fe-BEA zeolite (having a BET specific surface area of ​​1000 nm / g and a SiO2:Al2O3 molar ratio of 10:1). First, the available pore volume of the zeolite was determined, and based on this value, a volume of diluted palladium salt solution was made equal to the available pore volume. This diluted solution was then added dropwise to the Fe-BEA zeolite support over a period of 30 minutes with continuous stirring to obtain a wet material. The resulting material was then calcined in an oven at 590°C and cooled. After calcination, the resulting powder was mixed with distilled water to form an aqueous mixture with 40% solids, and the pH was adjusted to 3.75 with an organic acid. At this point, the slurry was milled until the particles of the mixture had a Dv90 of 10 micrometers. Separately, a Cu-CHA zeolite material (calculated as CuO based on the weight of Cu-CHA, Cu: 5.1 wt.%, Dv90 of 25 micrometers, SiO2:Al2O3 molar ratio of 18.5:1, and ca. 625 m 2 Cu-CHA (having a BET specific surface area of ​​1000 μm / g) was added to deionized water to form a mixture. Further, a soluble zirconium solution (30 wt% ZrO2) was added as a binder to the mixture containing water and Cu-CHA. The pH was adjusted to 7. The solids content of the final mixture was 38 wt%.

[0404] At this point, the Pd-impregnated Fe-BEA mixture was mixed into the Cu-CHA mixture and the pH was adjusted again to 7. The final mixture was mixed with the honeycomb flow-through monolith cordierite substrate (400 / (2.54) per square centimeter) 2 The mixture was then ready to be placed on a cylindrical substrate (10.5 in. diameter by 3 in. length, with a cell of 0.10 mm (4 mils) wall thickness). The substrate was coated with the final mixture according to the coating method defined in Example 4. A target of 2.4 g / in 3To achieve a washcoat loading of 2.05 g / in, the substrate was coated once over its entire length from the exit end to the inlet end of the substrate, with drying and calcination steps following the coating step. To dry the coated substrate, the substrate was placed in an oven at 90° C. for approximately 30 minutes. After drying, the coated substrate was calcined at 590° C. for 30 minutes. The final loading of coating in the catalyst after calcination was 2.05 g / in. 3 Cu-CHA, 0.25g / in 3 Fe-BEA, 0.1g / in 3 of zirconia (binder), and 15g / ft 3 Pd loading of 2.4g / in 3 It was.

[0405] Example 8: Preparation of a multifunctional catalyst according to the present invention 200m 2 Incipient wetness impregnation of Pd into aluminum oxide having a BET specific surface area of ​​1000 nm / g, a Dv50 of 3 micrometers, and a Dv90 of 16 micrometers. First, the available pore volume of the non-zeolitic oxide support was determined, and based on this value, a volume of diluted palladium salt solution was made equal to the available pore volume. This diluted solution was then added dropwise to the aluminum oxide support over a period of 30 minutes with continuous stirring to obtain a wet material. The resulting material was then calcined in an oven at 590°C and cooled. After calcination, the resulting powder was mixed with distilled water to form an aqueous mixture with 40% solids, and the pH was adjusted to 3.75 with an organic acid. At this point, the slurry was milled until the particles of the mixture had a Dv90 of 10 micrometers.

[0406] Separately, a Cu-CHA zeolite material (calculated as CuO based on the weight of Cu-CHA, Cu: 5.1 wt.%, Dv90 of 25 micrometers, SiO2:Al2O3 molar ratio of 18.5:1, and ca. 625 m 2 / g), and Fe-BEA zeolite material (Fe: 4.5 wt%, 600 m, calculated as Fe2O3 based on the weight of Fe-BEA). 2A mixture of Fe-BEA (with a BET specific surface area of ​​0.01 μm / g and a SiO2:Al2O3 molar ratio of 10:1) was added to deionized water in a mass ratio of about 9:1 to form a mixture. Further, a soluble zirconium solution (30 wt% ZrO2) was added as a binder to the mixture containing water, Fe-BEA, and Cu-CHA. The pH was adjusted to 7. The solids content of the final mixture was 38 wt%.

[0407] At this point, the Pd-impregnated Al2O3 mixture was mixed into the Cu-CHA / Fe-BEA mixture and the pH was adjusted back to 7. The final mixture was mixed with the honeycomb flow-through monolith cordierite substrate (400 / (2.54) per square centimeter) 2 The mixture was then ready to be placed on a cylindrical substrate (10.5 in. diameter by 3 in. length, with a cell of 0.10 mm (4 mils) wall thickness). The substrate was coated with the final mixture according to the coating method defined in Example 4. A target of 2.4 g / in 3 To achieve a washcoat loading of 1.8 g / in, the substrate was coated once over its entire length from the exit end to the inlet end of the substrate, with drying and calcination steps following the coating step. To dry the coated substrate, the substrate was placed in an oven at 90° C. for approximately 30 minutes. After drying, the coated substrate was calcined at 590° C. for 30 minutes. The final loading of coating in the catalyst after calcination was 1.8 g / in. 3 Cu-CHA, 0.25g / in 3 Fe-BEA, 0.25g / in 3 of Al2O3, 0.1g / in 3 of zirconia (binder), and 15g / ft 3 Pd loading of 2.4g / in 3 It was.

[0408] Example 9: Preparation of a multifunctional catalyst according to the present invention The catalyst of Example 9 was prepared by replacing an alumina oxide support with a zirconium oxide support (88% by weight ZrO2, 10% by weight La2O3, and 2% by weight HfO2, with a 67m 2The catalyst was prepared in the same manner as in Example 8, except that 1.8 g / in 2 CrN2O3 was used instead of 1.8 g / in 2 CrN2O3 (having a BET specific surface area of ​​1.8 g / in 2 , a Dv50 of 3 micrometers, and a Dv90 of 16 micrometers). The final loading of the coating in the catalyst after calcination was 1.8 g / in 2 . 3 Cu-CHA, 0.25g / in 3 Fe-BEA, 0.25g / in 3 Zirconia / HfO3 / La2O3, 0.1g / in 3 of zirconia (binder), and 15g / ft 3 Pd loading of 2.4g / in 3 It was.

[0409] Example 10: Preparation of a multifunctional catalyst according to the present invention 200m 2 Incipient wetness impregnation of Pd into aluminum oxide having a BET specific surface area of ​​1000 nm / g, a Dv50 of 3 micrometers, and a Dv90 of 16 micrometers. First, the available pore volume of the non-zeolitic oxide support was determined, and based on this value, a volume of diluted palladium salt solution was made equal to the available pore volume. This diluted solution was then added dropwise to the aluminum oxide support over a period of 30 minutes with continuous stirring to obtain a wet material. The resulting material was then calcined in an oven at 590°C and cooled. After calcination, the resulting powder was mixed with distilled water to form an aqueous mixture with 40% solids, and the pH was adjusted to 3.75 with an organic acid. At this point, the slurry was milled until the particles of the mixture had a Dv90 of 10 micrometers.

[0410] Separately, a Cu-CHA zeolite material (calculated as CuO based on the weight of Cu-CHA, Cu: 5.1 wt.%, Dv90 of 25 micrometers, SiO2:Al2O3 molar ratio of 18.5:1, and ca. 625 m 2 / g) and FER zeolite material in ammonium form (400 m 2A mixture of Cu-CHA and FER (having a BET specific surface area of ​​0.01 g / g and a SiO2:Al2O3 molar ratio of 20:1) was added to deionized water in a mass ratio of about 9:1 to form a mixture. Further, a soluble zirconium solution (30 wt% ZrO2) was added as a binder to the mixture containing water, FER, and Cu-CHA. The pH was adjusted to 7. The solids content of the final mixture was 38 wt%.

[0411] At this point, the Pd-impregnated Al2O3 mixture was mixed into the Cu-CHA / FER mixture and the pH was adjusted back to 7. The final mixture was mixed with the honeycomb flow-through monolith cordierite substrate (400 / (2.54) per square centimeter) 2 The mixture was then ready to be placed on a cylindrical substrate (10.5 in. diameter by 3 in. length, with a cell of 0.10 mm (4 mils) wall thickness). The substrate was coated with the final mixture according to the coating method defined in General Coating Methods. A target coating density of 2.4 g / in 3 To achieve a washcoat loading of 1.8 g / in, the substrate was coated once over its entire length from the exit end to the inlet end of the substrate, with drying and calcination steps following the coating step. To dry the coated substrate, the substrate was placed in an oven at 90° C. for approximately 30 minutes. After drying, the coated substrate was calcined at 590° C. for 30 minutes. The final loading of coating in the catalyst after calcination was 1.8 g / in. 3 Cu-CHA, 0.25g / in 3 FER, 0.25g / in 3 of Al2O3, 0.1g / in 3 of zirconia (binder), and 15g / ft 3 Pd loading of 2.4g / in 3 It was.

[0412] Example 11: Preparation of a multifunctional catalyst according to the present invention coating: Exit Court: Zirconium-based oxide support was placed in a 200m 2The exit coat of Example 11 was prepared similarly to the exit coat of Example 11, except that aluminum oxide having a BET specific surface area of ​​2.05 g / in 2 was substituted with aluminum oxide having a Dv50 of 3 micrometers and a Dv90 of 16 micrometers. The final loading of the exit coat in the catalyst after calcination was 2.05 g / in 2. 3 Cu-CHA, 0.24g / in 3 of Al2O3, 0.1g / in 3 of zirconia (binder), and 15g / ft 3 Pd loading of 2.4g / in 3 It was.

[0413] Entrance Court: 200m 2 Incipient wetness impregnation of Pd into aluminum oxide having a BET specific surface area of ​​1000 nm / g, a Dv50 of 3 micrometers, and a Dv90 of 16 micrometers. First, the available pore volume of the oxide support was determined, and based on this value, a volume of diluted palladium salt solution was made equal to the available pore volume. This diluted solution was then added dropwise to the aluminum oxide support over a period of 30 minutes with continuous stirring to obtain a wet material. The resulting material was then calcined in an oven at 590°C and cooled. After calcination, the resulting powder was mixed with distilled water to form an aqueous mixture with 40% solids, and the pH was adjusted to 3.75 with an organic acid. At this point, the slurry was milled until the particles of the mixture had a Dv90 of 10 micrometers.

[0414] Separately, iron-exchanged BEA zeolite material (4.5 wt.% Fe, calculated as Fe2O3 based on the weight of Fe-BEA, 600 m 2 A soluble zirconium solution (30 wt.% ZrO2) was added to the mixture containing water and Fe-BEA as a binder. The pH was adjusted to 7. The solids content of the final mixture was 38 wt.%.

[0415] At this point, the Pd-impregnated Al2O3 mixture was mixed into the Fe-BEA mixture and the pH was adjusted back to 7. The final mixture was ready to be placed onto the honeycomb flow-through monolith cordierite substrate. The final loading of the inlet coat in the catalyst after calcination was 2.05 g / in 3 Fe-BEA, 0.25g / in 3 of Al2O3, 0.1g / in 3 of zirconia (binder), and 15g / ft 3 Pd loading of 2.4g / in 3 It was.

[0416] Example 12: Preparation of a multifunctional catalyst according to the present invention 600m 2 Incipient wetness impregnation of Pd into a zeolite material having a framework type BEA in its H-form, with a BET specific surface area of ​​1000 / g and a SiO2:Al2O3 molar ratio of 800:1. First, the available pore volume of the zeolite was determined, and based on this value, a volume of diluted palladium salt solution was made equal to the available pore volume. This diluted solution was then added dropwise to the BEA zeolite support over a period of 30 minutes with continuous stirring to obtain a wet material. The resulting material was then calcined in an oven at 590°C and cooled. After calcination, the resulting powder was mixed with distilled water to form an aqueous mixture with 40% solids, and the pH was adjusted to 3.75 with an organic acid. At this point, the slurry was milled until the particles of the mixture had a Dv90 of 10 micrometers. Separately, a Cu-CHA zeolite material (calculated as CuO based on the weight of Cu-CHA, Cu: 5.1 wt.%, Dv90 of 25 micrometers, SiO2:Al2O3 molar ratio of 18.5:1, and ca. 625 m 2 Cu-CHA (having a BET specific surface area of ​​1000 μm / g) was added to deionized water to form a mixture. Further, a soluble zirconium solution (30 wt% ZrO2) was added as a binder to the mixture containing water and Cu-CHA. The pH was adjusted to 7. The solids content of the final mixture was 38 wt%.

[0417] At this point, the Pd-impregnated BEA mixture was mixed into the Cu-CHA mixture and the pH was adjusted back to 7. The final mixture was mixed with the honeycomb flow-through monolith cordierite substrate (400 / (2.54) per square centimeter) 2 The mixture was then ready to be placed on a cylindrical substrate (10.5 in. diameter by 3 in. length, with a cell of 0.10 mm (4 mils) wall thickness). The substrate was coated with the final mixture according to the coating method defined in General Coating Methods. A target coating density of 2.4 g / in 3 To achieve a washcoat loading of 2.05 g / in, the substrate was coated once over its entire length from the exit end to the inlet end of the substrate, with drying and calcination steps following the coating step. To dry the coated substrate, the substrate was placed in an oven at 90° C. for approximately 30 minutes. After drying, the coated substrate was calcined at 590° C. for 30 minutes. The final loading of coating in the catalyst after calcination was 2.05 g / in. 3 Cu-CHA, 0.25g / in 3 BEA, 0.1g / in 3 of zirconia (binder), and 15g / ft 3 Pd loading of 2.4g / in 3 It was.

[0418] Example 13: Preparation of a multifunctional catalyst according to the present invention 200m 2Incipient wetness impregnation of Pd into aluminum oxide having a BET specific surface area of ​​1000 nm / g, a Dv50 of 3 micrometers, and a Dv90 of 16 micrometers. First, the available pore volume of the oxide support was determined, and based on this value, a volume of diluted palladium salt solution was made equal to the available pore volume. This diluted solution was then added dropwise to the aluminum oxide support over a period of 30 minutes with continuous stirring to obtain a wet material. The resulting material was then calcined in an oven at 590°C and cooled. After calcination, the resulting powder was mixed with distilled water to form an aqueous mixture with 40% solids, and the pH was adjusted to 3.75 with an organic acid. At this point, the slurry was milled until the particles of the mixture had a Dv90 of 10 micrometers. Separately, a Cu-CHA zeolite material (calculated as CuO based on the weight of Cu-CHA, Cu: 5.1 wt.%, Dv90 of 25 micrometers, SiO2:Al2O3 molar ratio of 18.5:1, and ca. 625 m 2 / g BET specific surface area), and 600 m 2 BEA zeolite material in its H-form, having a BET specific surface area of ​​1000 / g and a SiO2:Al2O3 molar ratio of 800:1, was added to deionized water in a mass ratio of about 9:1 to form a mixture. Further, a soluble zirconium solution (30 wt.% ZrO2) was added as a binder to the mixture containing water, BEA, and Cu-CHA. The pH was adjusted to 7. The solids content of the final mixture was 38 wt.%.

[0419] At this point, the Pd-impregnated Al2O3 mixture was mixed into the Cu-CHA / BEA mixture and the pH was adjusted back to 7. The final mixture was mixed with the honeycomb flow-through monolith cordierite substrate (400 / (2.54) per square centimeter) 2 The mixture was then ready to be placed on a cylindrical substrate (10.5 in. diameter by 3 in. length, with a cell of 0.10 mm (4 mils) wall thickness). The substrate was coated with the final mixture according to the coating method defined in General Coating Methods. A target coating density of 2.4 g / in 3To achieve a washcoat loading of 1.8 g / in, the substrate was coated once over its entire length from the exit end to the inlet end of the substrate, with drying and calcination steps following the coating step. To dry the coated substrate, the substrate was placed in an oven at 90° C. for approximately 30 minutes. After drying, the coated substrate was calcined at 590° C. for 30 minutes. The final loading of coating in the catalyst after calcination was 1.8 g / in. 3 Cu-CHA, 0.25g / in 3 BEA, 0.25g / in 3 of Al2O3, 0.1g / in 3 of zirconia (binder), and 15g / ft 3 Pd loading of 2.4g / in 3 It was.

[0420] Example 14: Preparation of a multifunctional catalyst according to the present invention The catalyst of Example 14 was prepared similarly to the catalyst of Example 10, except that palladium was replaced with platinum. The final loading of the coating in the catalyst after calcination was 1.8 g / in 3 Cu-CHA, 0.25g / in 3 FER, 0.25g / in 3 of Al2O3, 0.1g / in 3 of zirconia (binder), and 15g / ft 3 Pt loading of 2.4g / in 3 It was.

[0421] Example 15: Preparation of a multifunctional catalyst according to the present invention First (bottom) coating: Si-doped titania powder (10% by mass SiO2, 200 m 2A platinum ammine solution was added to the Cu-CHA zeolite material (CHA with SiO2:Al2O3 molar ratio of 18:1, Cu:5.1 wt%, calculated as CuO based on the weight of Cu-CHA) to achieve 5 wt% ZrO2 after calcination based on the weight of the zeolite material. The Pt-containing slurry was added to the Cu-CHA slurry and stirred to produce the final slurry. An uncoated honeycomb flow-through cordierite monolith substrate (400 / (2.54) per square centimeter) was then milled to obtain a Pt content of 0.46 wt% Pt based on the weight of the Si-titania. This material was added to water and the slurry was milled until the resulting Dv90 was 10 micrometers. A zirconyl-acetate solution was added to the aqueous slurry of Cu-CHA zeolite material (CHA with SiO2:Al2O3 molar ratio of 18:1, Cu:5.1 wt%, calculated as CuO based on the weight of Cu-CHA) to achieve 5 wt% ZrO2 after calcination based on the weight of the zeolite material. The Pt-containing slurry was added to the Cu-CHA slurry and stirred to produce the final slurry. An uncoated honeycomb flow-through cordierite monolith substrate (400 / (2.54) per square centimeter) was then milled to obtain a Pt content of 0.46 wt% Pt based on the weight of the Si-titania. 2 This final slurry was placed on a 10.5 in. diameter by 3 in. cylindrical substrate with 1.0 mm cells and 0.10 mm (4 mil) wall thickness from the outlet end to the inlet end over 50% of the substrate's axial length. The substrate was then dried at 120° C. for 10 minutes and 160° C. for 30 minutes, and then calcined at 450° C. for 30 minutes. After calcination, the loading of the first coating was 0.25 g / in. 3 Cu-CHA loading, 0.04 g / in 3 ZrO2 loading, 0.21 g / in 3 Si-titania loading and 5g / ft 3 With a Pt loading of about 0.5 g / in 3 It was.

[0422] Second (top) coating: The slurry for preparing the second coating was prepared similarly to the slurry for preparing the coating of Example 10. This slurry was then placed over the entire length of the substrate coated with the first coating, from the exit end to the entrance end, according to the general coating method (Reference Example 4). 3To achieve a washcoat loading of 1.8 g / in, the substrate was coated once over its entire length from the exit end to the inlet end of the substrate, with drying and calcination steps following the coating step. To dry the coated substrate, the substrate was placed in an oven at 90° C. for approximately 30 minutes. After drying, the coated substrate was calcined at 590° C. for 30 minutes. The final loading of the second (top) coating in the catalyst after calcination was 1.8 g / in. 3 Cu-CHA, 0.25g / in 3 FER, 0.25g / in 3 of Al2O3, 0.1g / in 3 of zirconia (binder), and 15g / ft 3 Pd loading of 2.4g / in 3 It was.

[0423] Example 16: Testing of multifunctional catalysts of Examples 10 and 12-15 - DeNOx, N2O production and NH3 slip Testing of the fresh catalyst was carried out in a heavy duty diesel engine at steady state. DeNOx, N2O production and NH3 slip were measured under different conditions: - 200 °C, with an exhaust flow rate of about 250 kg / h; about 1000 ppm NOx (measurements were taken after a stabilization time of 20 minutes; the average values ​​reported in the figures were calculated for the last 2 minutes after stabilization); - 350°C, with an exhaust flow rate of about 250 kg / h; NOx of about 1800 ppm (measurements were taken after a stabilization time of 20 minutes; the average values ​​reported in the figures were calculated for the last 2 minutes after stabilization).

[0424] The results are shown in Figures 8 to 10.

[0425] Comments on Examples 10, 12 and 13 (Pd only): As can be seen from Figures 8 and 9, all Pd-based multifunctional catalysts (MFCs) showed comparable DeNOx at both low and high temperatures. The MFCs containing zeolites with high Si / Al ratios (Examples 12 and 13) showed higher NO production than the MFC of Example 10.

[0426] Comments on Examples 14 and 15 (containing Pt): As can be seen from Figures 9 and 10, when Pt is included in the MFC instead of Pd (Example 14), the MFC shows lower DeNOx at high temperatures (due to the oxidation of NH3, which mainly occurs at high temperatures), and consequently lower NH3 slip. At the same time, the MFC with only Pt shows higher N2O production. Furthermore, as can be seen from Figures 8-10, when a PGM-containing bottom coat (=AMOX) is included in the MFC (Example 15), the high temperature DeNOx is not affected compared to Example 14, showing a low temperature DeNOx equivalent to all other MFCs. At the same time, the NH3 slip is low, i.e., less than 10 ppm, while the production of N2O is significantly lower than in Example 14. Without wishing to be bound by any theory, it is noted that the low temperature NH3 slip is largely influenced by the storage effect, since Pt is not active for NH3 oxidation at 200 °C.

[0427] References - WO 2018 / 224651 A2 - US 10,589,261 B2 - US 5788 834 B

Claims

1. (i) a substrate including an inlet end, an outlet end, an axial length of the substrate extending from the inlet end to the outlet end, and a plurality of passages defined by an interior wall of the substrate extending therethrough; (ii) a coating disposed on a surface of an inner wall of a substrate, the coating comprising an 8-ring porous zeolite material comprising a platinum group metal and one or more of copper and iron, and further comprising a 10-ring or greater porous zeolite material. Catalysts for selective catalytic reduction of NOx and cracking and conversion of hydrocarbons, comprising:

2. 2. The catalyst of claim 1, wherein the coating (ii) further comprises a non-zeolitic oxide material comprising one or more of alumina, zirconia, silica, titania and ceria, preferably one or more of alumina, zirconia and silica, more preferably one or more of alumina and zirconia, more preferably alumina or zirconia.

3. 3. The catalyst according to claim 1 or 2, wherein the 8-ring porous zeolitic material comprised in said coating (ii) is selected from the group consisting of CHA, AEI, RTH, LEV, DDR, KFI, ERI, AFX, mixtures of two or more thereof and mixed types of two or more thereof, preferably selected from the group consisting of CHA, AEI, RTH, AFX, mixtures of two or more thereof and mixed types of two or more thereof, more preferably has a framework type selected from the group consisting of CHA and AEI, more preferably the 8-ring porous zeolitic material comprised in said coating (ii) has framework type CHA.

4. Catalyst according to claim 1, wherein the porous zeolitic material with 10 or more ring members contained in the coating (ii) is selected from the group consisting of FER, MFI, BEA, MWW, AFI, MOR, OFF, MFS, MTT, FAU, LTL, MEI, MOR, mixtures of two or more thereof and mixed types of two or more thereof, preferably selected from the group consisting of FAU, FER, MFI, BEA, MWW, MOR, mixtures of two or more thereof and mixed types of two or more thereof, more preferably a zeolitic material having a framework type selected from the group consisting of FAU, FER, MFI and BEA, more preferably the porous zeolitic material with 10 or more ring members, preferably a porous zeolitic material with 10 or 12 ring members, is a zeolitic material having framework type FAU or FER or MFI or BEA.

5. Catalyst according to claim 1, wherein the platinum group metal contained in said coating (ii) is palladium.

6. In the framework structure of the porous zeolite material having 10 or more ring members contained in the coating (ii), 2 :Al 2 O 3 2. The catalyst of claim 1, wherein the molar ratio of Si to Al, calculated as: is in the range of 2:1 to 60:

1.

7. The porous zeolite material having 10 or more ring members contained in the coating (ii) is a zeolite material having a BEA framework, and the framework structure of the zeolite material has a molar SiO 2 :Al 2 O 3 the molar ratio of Si to Al, calculated as: is in the range of 4:1 to 20:1, preferably in the range of 6:1 to 15:1, more preferably in the range of 8:1 to 12:1; or The porous zeolite material having 10 or more ring members contained in the coating (ii) is a zeolite material having a framework type FER, and in the framework structure of the zeolite material, 2 :Al 2 O 3 2. The catalyst of claim 1, wherein the molar ratio of Si to Al, calculated as: is in the range of 10:1 to 30:1, preferably in the range of 15:1 to 25:1, more preferably in the range of 18:1 to 22:

1.

8. The porous zeolite material having 10 or more ring members contained in the coating (ii) is a zeolite material having a framework type FAU, and in the framework structure of the zeolite material, 2 :Al 2 O 3 the molar ratio of Si to Al, calculated as: is in the range of 3:1 to 15:1, preferably in the range of 4:1 to 10:1, more preferably in the range of 4:1 to 8:1; or The porous zeolite material having 10 or more ring members contained in the coating (ii) is a zeolite material having a framework type MFI, and in the framework structure of the zeolite material, 2 :Al 2 O 3 2. The catalyst of claim 1, wherein the molar ratio of Si to Al, calculated as: is in the range of 10:1 to 35:1, preferably in the range of 20:1 to 32:1, more preferably in the range of 25:1 to 30:

1.

9. the 10 or more ring-membered porous zeolitic material in the coating (ii) comprises one or more of iron, copper and rare earth element components, preferably one or more of iron and rare earth element components; 2. The catalyst according to claim 1, wherein the coating (ii) comprises one or more of the iron, copper and rare earth element components, calculated as the respective oxides, preferably in an amount in the range of 1 to 20% by weight, more preferably in the range of 5 to 20% by weight, more preferably in the range of 10 to 20% by weight, based on the weight of the porous zeolitic material having 10 or more ring members contained in the coating (ii).

10. (ii) said coating (ii.1) an inlet coat comprising a platinum group metal and a porous zeolite material having 10 or more ring members; and (ii.2) an outlet coat comprising a platinum group metal, a non-zeolitic oxide material, and an 8-ring porous zeolitic material comprising one or more of copper and iron; and preferably consisting of the above, said inlet coat (ii.1) extends from the inlet end towards the outlet end of said substrate according to (i) over x % of the axial length of the substrate, x being in the range of 20 to 80, preferably 30 to 60; 2. The catalyst of claim 1, wherein the outlet coat (ii.2) extends from the outlet end towards the inlet end of the substrate according to (i) over y % of the axial length of the substrate, where y is in the range of 20 to 80, preferably 30 to 60.

11. or the platinum group metal in the inlet coat (ii.1) is palladium and the 10 or more ring porous zeolitic material in the inlet coat (ii.1) is a zeolitic material having framework type BEA, the zeolitic material preferably comprising one or more of iron, copper and rare earth element components, more preferably one or more of iron and rare earth element components, more preferably iron; or The platinum group metal in the inlet coat (ii.1) is palladium and the 10 or more ring porous zeolitic material in the inlet coat (ii.1) is a zeolitic material having framework type FAU, the zeolitic material preferably comprising one or more of iron, copper and rare earth element components, more preferably one or more of iron and rare earth element components, more preferably a rare earth element component; or Catalyst according to claim 10, wherein the platinum group metal in the inlet coat (ii.1) is palladium and the 10 or more ring porous zeolitic material in the inlet coat (ii.1) is a zeolitic material with framework type MFI, said zeolitic material preferably comprising one or more of iron, copper and rare earth element components, more preferably one or more of iron and rare earth element components, more preferably iron.

12. In the framework structure of the 8-ring porous zeolitic material of the outlet coat (ii.2), molar SiO 2 :Al 2 O 3 11. The catalyst of claim 10, wherein the molar ratio of Si to Al, calculated as: is in the range of 15:1 to 33:1, preferably in the range of 15:1 to 20:1, or preferably in the range of 25:1 to 33:

1.

13. 2. The catalyst of claim 1, wherein said coating (ii) is a single coat.

14. In the framework structure of the eight-ring porous zeolite material of the coating (ii), the molar SiO 2 :Al 2 O 3 The catalyst according to claim 13, wherein the molar ratio of Si to Al, calculated as: is more preferably in the range of 15:1 to 20:

1.

15. Catalyst according to claim 13, wherein the mass ratio of the 8-ring porous zeolitic material of said coating (ii) to the 10 or more ring porous zeolitic material of said coating (ii) is in the range of 2:1 to 15:1, preferably in the range of 3:1 to 12:1, more preferably in the range of 5:1 to 9:

1.

16. the 8-ring porous zeolitic material of said coating (ii) has framework type CHA and the 10 or more ring porous zeolitic material of said coating (ii) has framework type BEA and contains iron; or Catalyst according to claim 13, wherein the 8-ring porous zeolitic material of the coating (ii) has a framework type CHA and the 10 or more ring porous zeolitic material of the coating (ii) has a framework type FAU and comprises a rare earth element component.

17. the 8-ring porous zeolitic material of said coating (ii) having framework type CHA and the 10 or more ring porous zeolitic material of said coating (ii) having framework type MFI and containing iron; or Catalyst according to claim 14, wherein the 8-ring porous zeolitic material of the coating (ii) has framework type CHA and the 10 or more ring porous zeolitic material of the coating (ii) has framework type FER.

18. 10. A method of using the catalyst of claim 1 for selective catalytic reduction of NOx and decomposition and conversion of hydrocarbons, for simultaneously selective catalytic reduction of NOx and decomposition and conversion of hydrocarbons.

19. 1. An exhaust gas treatment system for treating an exhaust gas stream from a diesel engine, the exhaust gas treatment system having an upstream end for introducing the exhaust gas stream into the exhaust gas treatment system, the exhaust gas treatment system comprising: (a) a first catalyst having an inlet end and an outlet end, said catalyst being the catalyst of claim 1; (b) a second catalyst having an inlet end and an outlet end and comprising a coating disposed on a substrate, the coating comprising a platinum group metal supported on a non-zeolitic oxide material and further comprising one or more of vanadium oxide, tungsten oxide, and a zeolitic material comprising one or more of copper and iron; Including, the first catalyst according to (a) is a first catalyst of the exhaust gas treatment system downstream of the upstream end of the exhaust gas treatment system, the inlet end of the first catalyst being disposed upstream of the outlet end of the first catalyst; In the exhaust gas treatment system, the second catalyst according to (b) is disposed downstream of the first catalyst according to (a), and the inlet end of the second catalyst is disposed upstream of the outlet end of the second catalyst.

20. a substrate including an inlet end, an outlet end, an axial length of the substrate extending from the inlet end to the outlet end, and a plurality of passages defined by an interior wall of the substrate extending therethrough; - a first coating disposed on a surface of an interior wall of the substrate, the coating comprising a platinum group metal supported on a non-zeolitic oxide material and further comprising one or more of vanadium oxide, tungsten oxide, and a zeolitic material comprising one or more of copper and iron; a second coating disposed on said first coating, said coating comprising an 8-ring porous zeolite material comprising one or more of a platinum group metal, copper and iron, and further comprising a 10-ring or greater porous zeolite material; Catalysts for selective catalytic reduction of NOx, cracking and conversion of hydrocarbons, and oxidation of ammonia, including